1,10]Phenanthroline based cyanine dyes as fluorescent probes for ribonucleic acids in live cells - Kovalska, Vladyslava B.; Kuperman, Marina; Varzatskii, Oleg; Kryvorotenko, Dmytro; Kinski, Elisa; Schikora, Margot; Janko, Christina; Alexiou, Christoph; Yarmoluk, Sergiy; Mokhir, Andriy (Methods and Applications in Fluorescence, 2017)
A series of monomethine, trimethine- and styrylcyanine dyes based on a [1,10]phenanthroline moiety was synthesized, characterized and investigated as potential fluorescent probes for nucleic acids in cell free settings and in cells. The dyes were found to be weakly fluorescent in the unbound state, whereas upon the binding to dsDNA or RNA their emission intensity raised up to 50 times (for monomethine benzothiazole derivative FT1 complexed with RNA). The strongest fluorescence intensity in assemblies with dsDNA and RNA was observed for the trimethine benzothiazole derivative FT4. The quantum yield of FT4 fluorescence in its complex with dsDNA was found to be 1.5% and the binding constant (K b) was estimated to be 7.9 × 104 M-1 that is a typical value for intercalating molecules. The FT4 dye was found to be cell membrane permeable. It stains RNA rich components-the nucleoli and most probably the cytoplasmic RNA. FT4 bound to RNAs delivers a very strong fluorescence signal, which makes this easily accessible dye a potentially useful alternative to known RNA stains, e.g. expensive SYTO® 83. The advantage of FT4 is its easy synthetic access including no chromatographic purification steps, which will be reflected in its substantially lower price.
EVALuna2:35777

Adhesion/growth-regulatory galectins in the human eye: localization profiles and tissue reactivities as a standard to detect disease-associated alterations - Schlötzer-Schrehardt, Ursula; Andre, Sabine; Janko, Christina; Kaltner, Herbert; Kopitz, Juergen; Gabius, Hans-Joachim; Herrmann, Martin (Graefes Archive For Clinical and Experimental Ophthalmology, 2012)
To characterize the localization profiles of seven adhesion/growth-regulatory galectins in the normal human eye using immunodetection of endogenous galectins and binding of labeled galectins to sections, useful as a basis to detect disease-associated alterations.Non-cross-reactive anti-galectin antibodies and biotinylated galectins were tested on acetone-fixed cryosections of normal human donor eyes. Controls included omission of first-step reagent, testing of an antibody against a galectin specific for rat (galectin-5), and blocking of galectin binding with lactose.Galectin presence was not restricted to one or few members of this family. Signal occurrence can even include all tested or most proteins (conjunctival or corneal epithelium), whereas choroid positivity is fully accounted for by galectin-9. Regional specificity and characteristic profiles for each protein, immuno- and galectin histochemically, were determined. Differences in tissue reactivity among the galectins were detected.That the galectins have characteristic localization/reactivity profiles supports the concept of a network with potential for non-overlapping functions. The reported data thus prompt to proceed to the respective analysis of specimens from ocular diseases.
EVALuna2:12715

Aggregated neutrophil extracellular traps limit inflammation by degrading cytokines and chemokines - Schauer, Christine; Janko, Christina; Munoz Becerra, Luis; Zhao, Yi; Kienhöfer, Deborah; Frey, Benjamin; Lell, Michael; Manger, Bernhard; Rech, Juergen; Naschberger, Elisabeth; Holmdahl, Rikard; Krenn, Veit; et al. (Nature Medicine, 2014)
Gout is characterized by an acute inflammatory reaction and the accumulation of neutrophils in response to monosodium urate (MSU) crystals. Inflammation resolves spontaneously within a few days, although MSU crystals can still be detected in the synovial fluid and affected tissues. Here we report that neutrophils recruited to sites of inflammation undergo oxidative burst and form neutrophil extracellular traps (NETs). Under high neutrophil densities, these NETs aggregate and degrade cytokines and chemokines via serine proteases. Tophi, the pathognomonic structures of chronic gout, share characteristics with aggregated NETs, and MSU crystals can induce NETosis and aggregation of NETs. In individuals with impaired NETosis, MSU crystals induce uncontrolled production of inflammatory mediators from neutrophils and persistent inflammation. Furthermore, in models of neutrophilic inflammation, NETosis-deficient mice develop exacerbated and chronic disease that can be reduced by adoptive transfer of aggregated NETs. These findings suggest that aggregated NETs promote the resolution of neutrophilic inflammation by degrading cytokines and chemokines and disrupting neutrophil recruitment and activation.
Created from Fastlane, Scopus look-up

Altered glycan accessibility on native immunoglobulin G complexes in early rheumatoid arthritis and its changes during therapy - Stuemer, J.; Biermann, Mona; Knopf, Jasmin; Magorivska, I.; Kastbom, A.; Svaerd, A.; Janko, Christina; Bilyy, R.; Schett, Georg; Sjoewall, C.; Herrmann, Martin; Munoz, Luis Enrique; et al. (Clinical and Experimental Immunology, 2017)
The goal of this study was to investigate the glycosylation profile of native immunoglobulin (Ig)G present in serum immune complexes in patients with rheumatoid arthritis (RA). To accomplish this, lectin binding assays, detecting the accessibility of glycans present on IgG-containing immune complexes by biotinylated lectins, were employed. Lectins capturing fucosyl residues (AAL), fucosylated tri-mannose N-glycan core sites (LCA), terminal sialic acid residues (SNA) and O-glycosidically linked galactose/N-acetylgalactosamine (GalNac-L) were used. Patients with recent-onset RA at baseline and after 3-year follow-up were investigated. We found that native IgG was complexed significantly more often with IgM, C1q, C3c and C-reactive protein (CRP) in RA patients, suggesting alterations of the native structure of IgG. The total accessibility of fucose residues on captured immune complexes to the respective lectin was significantly higher in patients with RA. Moreover, fucose accessibility on IgG-containing immune complexes correlated positively with the levels of antibodies to cyclic citrullinated peptides (anti-CCP). We also observed a significantly higher accessibility to sialic acid residues and galactose/GalNAc glyco-epitopes in native complexed IgG of patients with RA at baseline. While sialic acid accessibility increased during treatment, the accessibility of galactose/GalNAc decreased. Hence, successful treatment of RA was associated with an increase in the SNA/GalNAc-L ratio. Interestingly, the SNA/GalNAc-L ratio in particular rises after glucocorticoid treatment. In summary, this study shows the exposure of glycans in native complexed IgG of patients with early RA, revealing particular glycosylation patterns and its changes following pharmaceutical treatment.
EVALuna2:13418

Altered glycosylation of complexed native IgG molecules is associated with disease activity of systemic lupus erythematosus - Sjowall, Christopher; Zapf, J.; Von Loehneysen, S.; Magorivska, I.; Biermann, M.; Janko, Christina; Winkler, Sophie; Bilyy, R.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Lupus, 2015)
In addition to the redundancy of the receptors for the Fc portion of immunoglobulins, glycans result in potential ligands for a plethora of lectin receptors found in immune effector cells. Here we analysed the exposure of glycans containing fucosyl residues and the fucosylated tri-mannose N-type core by complexed native IgG in longitudinal serum samples of well-characterized patients with systemic lupus erythematosus. Consecutive serum samples of a cohort of 15 patients with systemic lupus erythematosus during periods of increased disease activity and remission were analysed. All patients fulfilled the 1982 American College of Rheumatology classification criteria. Sera of 15 sex- and age-matched normal healthy blood donors served as controls. The levels and type of glycosylation of complexed random IgG was measured with lectin enzyme-immunosorbent assays. After specifically gathering IgG complexes from sera, biotinylated lectins Aleuria aurantia lectin and Lens culinaris agglutinin were employed to detect IgG-associated fucosyl residues and the fucosylated tri-mannose N-glycan core, respectively. In sandwich-ELISAs, IgG-associated IgM, IgA, C1q, C3c and C-reactive protein (CRP) were detected as candidates for IgG immune complex constituents. We studied associations of the glycan of complexed IgG and disease activity according to the physician's global assessment of disease activity and the systemic lupus erythematosus disease activity index 2000 documented at the moment of blood taking. Our results showed significantly higher levels of Aleuria aurantia lectin and Lens culinaris agglutinin binding sites exposed on IgG complexes of patients with systemic lupus erythematosus than on those of normal healthy blood donors. Disease activity in systemic lupus erythematosus correlated with higher exposure of Aleuria aurantia lectin-reactive fucosyl residues by immobilized IgG complexes. Top levels of Aleuria aurantia lectin-reactivity were found in samples taken during the highest activity of systemic lupus erythematosus. Our results show that native circulating IgG complexes from active systemic lupus erythematosus patients expose fucosyl residues and their glycan core is accessible to soluble lectins. Two putative mechanisms may contribute to the increased exposure of these glycans: (1) the canonical N-glycosylation site of the IgG-CH2 domain; (2) an IgG binding non-IgG molecule, like complement or C-reactive protein. In both cases the complexed IgG may be alternatively targeted to lectin receptors of effector cells, e.g. dendritic cells.
EVALuna2:13017

Analysis of Hypericin-Mediated Effects and Implications for Targeted Photodynamic Therapy - Mühleisen, Laura; Alev, Magdalena; Unterweger, Harald; Subatzus, Daniel; Poettler, Marina; Friedrich, Ralf P.; Alexiou, Christoph; Janko, Christina (International Journal of Molecular Sciences, 2017)
The phototoxic effect of hypericin can be utilized for Photodynamic Therapy (PDT) of cancer. After intravenous application and systemic distribution of the drug in the patient's body, the tumor site is exposed to light. Subsequently, toxic reactive oxygen species (ROS) are generated, inducing tumor cell death. To prevent unwanted activation of the drug in other regions of the body, patients have to avoid light during and after the treatment cycles, consequently impairing quality of life. Here, we characterize toxicity and hypericin-mediated effects on cancer cells in vitro and confirm that its effect clearly depends on concentration and illumination time. To reduce side effects and to increase therapy success, selective accumulation of hypericin in the tumor region is a promising solution. Loading hypericin on superparamagnetic iron oxide nanoparticles (SPIONs) and guiding them to the desired place using an external magnetic field might accomplish this task (referred to as Magnetic Drug Targeting (MDT)). Thus, using a double targeting strategy, namely magnetic accumulation and laser induced photoactivation, might improve treatment effectivity as well as specificity and reduce toxic side effects in future clinical applications.
EVALuna2:33199

Analyzing iron oxide nanoparticles for drug delivery - innovative investigation tools for nanotoxicology - Janko, Christina; Poettler, M.; Friedrich, Ralf P.; Zaloga, Jan; Unterweger, Harald; Dürr, Stephan; Tietze, Rainer; Cicha, Iwona; Lyer, Stefan; Alexiou, Christoph (2016)
EVALuna2:33178

An Endoplasmic Reticulum Specific Pro-amplifier of Reactive Oxygen Species in Cancer Cells - Xu, Honggui; Schikora, Margot; Sisa, Miroslav; Daum, Steffen; Klemt, Insa; Janko, Christina; Alexiou, Christoph; Bila, Galyna; Bilyy, Rostyslav; Gong, Wenjie; Schmitt, Michael; Sellner, Leopold; et al. (Angewandte Chemie International Edition, 2021)
The folding and export of proteins and hydrolysis of unfolded proteins are disbalanced in the endoplasmic reticulum (ER) of cancer cells, leading to so-called ER stress. Agents further augmenting this effect are used as anticancer drugs including clinically approved proteasome inhibitors bortezomib and carfilzomib. However, these drugs can affect normal cells, which also rely strongly on ER functions, leading, for example, to accumulation of reactive oxygen species (ROS). To address this problem, we have developed ER-targeted prodrugs activated only in cancer cells in the presence of elevated ROS amounts. These compounds are conjugates of cholic acid with N-alkylaminoferrocene-based prodrugs. We confirmed their accumulation in the ER of cancer cells, their anticancer efficacy, and cancer cell specificity. These prodrugs induce ER stress, attenuate mitochondrial membrane potential, and generate mitochondrial ROS leading to cell death via necrosis. We also demonstrated that the new prodrugs are activated in vivo in Nemeth-Kellner lymphoma (NK/Ly) murine model.
CRIS-Team WoS Importer:2021-04-16

An in silico model of the capturing of magnetic nanoparticles in tumour spheroids in the presence of flow - Wirthl, Barbara; Janko, Christina; Lyer, Stefan; Schrefler, Bernhard A.; Alexiou, Christoph; Wall, Wolfgang A. (Biomedical Microdevices, 2023)
One of the main challenges in improving the efficacy of conventional chemotherapeutic drugs is that they do not reach the cancer cells at sufficiently high doses while at the same time affecting healthy tissue and causing significant side effects and suffering in cancer patients. To overcome this deficiency, magnetic nanoparticles as transporter systems have emerged as a promising approach to achieve more specific tumour targeting. Drug-loaded magnetic nanoparticles can be directed to the target tissue by applying an external magnetic field. However, the magnetic forces exerted on the nanoparticles fall off rapidly with distance, making the tumour targeting challenging, even more so in the presence of flowing blood or interstitial fluid. We therefore present a computational model of the capturing of magnetic nanoparticles in a test setup: our model includes the flow around the tumour, the magnetic forces that guide the nanoparticles, and the transport within the tumour. We show how a model for the transport of magnetic nanoparticles in an external magnetic field can be integrated with a multiphase tumour model based on the theory of porous media. Our approach based on the underlying physical mechanisms can provide crucial insights into mechanisms that cannot be studied conclusively in experimental research alone. Such a computational model enables an efficient and systematic exploration of the nanoparticle design space, first in a controlled test setup and then in more complex in vivo scenarios. As an effective tool for minimising costly trial-and-error design methods, it expedites translation into clinical practice to improve therapeutic outcomes and limit adverse effects for cancer patients.
CRIS-Team Scopus Importer:2023-12-08
Keywords: Cylindrical permanent magnet; Magnetic drug targeting; Magnetic nanoparticles; Multiphase porous media; Tumour-growth model

A Novel Magnetic Field Device for Inducing Hyperthermia Using Magnetic Nanoparticles - Dürr, Stephan; Schmidt, Oliver; Janko, Christina; Kraemer, H P; Tripal, Philipp; Eiermann, F; Tietze, R; Lyer, Stefan; Alexiou, Christoph (Biomedizinische Technik, 2013)
A new alternating current (AC) magnetic field applicator was designed to induce hyperthermia in an animal tumour model using superparamagnetic iron oxidenanoparticles (SPION). First experiments on phantoms including different concentrations of SPION were conducted.The results confirmed that the new AC magnetic field applicator could heat-p SPION. This proofs the capability to induce hyperthermia by SPION, dependent on the concentration
EVALuna2:19922
Keywords: Magnetic drug targeting; nanoparticles; alternating current magnetic field; hyperthermia

Assessing Cytotoxicity, Endotoxicity, and Blood Compatibility of Nanoscale Iron Oxide Magnetosomes for Biomedical Applications - Mickoleit, Frank; Pfister, Felix; Friedrich, Bernhard; Markert, Simon; Kerpes, Andrea; Janko, Christina; Lyer, Stefan; Alexiou, Christoph; Schüler, Dirk; Tietze, Rainer (ACS Applied Nano Materials, 2024)
Magnetosomes are biogenic magnetic nanoparticles with unique material properties, such as high crystallinity and strong magnetization as well as uniform and tunable shapes and sizes. In particular, the ability to genetically modify their enveloping membrane could render isolated magnetosomes as versatile tools for a variety of potential applications in the biomedical field. However, the biocompatibility of the bacterially produced particles has so far not been fully been assessed. In this study, different biocompatibility and toxicity factors of magnetosomes isolated from the model organism Magnetospirillum gryphiswaldense were investigated and tested with THP-1, Jurkat cells, and primary human-derived material such as peripheral blood mononuclear cells (PBMCs). The obtained data demonstrate generally good biocompatibility for all tested magnetosome concentrations as well as high blood compatibility. Only slight but not significant complement activation was observed, with no indications for plasma coagulation or hemolysis. However, the presence of lipopolysaccharides originating from the Gram-negative cell wall of M. gryphiswaldense caused activation of PBMCs expressed as significant cytokine release. Thus, this endotoxicity represents an issue for possible in vivo applications, which needs to be addressed in future studies. Nevertheless, the results show that, overall, magnetosomes have high potential for different (bio)medical applications and are already well-suited for the fields of in vitro diagnostics.
CRIS-Team Scopus Importer:2024-01-26
Keywords: biocompatibility; biogenic magnetic nanoparticles; blood compatibility; endotoxicity; magnetosomes

Autoantibodies against galectins are associated with antiphospholipid syndrome in patients with systemic lupus erythematosus - Sarter, Kerstin; Janko, Christina; Andre, Sabine; Munoz, Luis Enrique; Schorn, Christine; Winkler, Sophie; Rech, Jürgen; Kaltner, Herbert; Lorenz, Hanns-Martin; Schiller, Martin; Andreoli, Laura; Manfredi, Angelo A.; et al. (Glycobiology, 2013)
The presence of autoantibodies against immunoregulatory effectors can be relevant for onset and/or the progression of autoimmune disease. Emerging insights into an immunological activity profile including a role as opsonins give reason to systematically monitor sera of patients for immunoglobulin G (IgG) autoantibodies, preferably for several galectins at the same time. Here, we report on a study of chronic inflammatory rheumatic diseases, i.e. systemic lupus erythematosus (SLE; pilot cohort p, n = 40; confirmation cohort c, n = 109), rheumatoid arthritis (RA; p, n = 32; c, n = 25) and primary antiphospholipid syndrome (APS; c, n = 64). Enzyme-linked immunosorbent assay-based series using galectin-1, -2, -3, -4, -7, -8 and -9 and natural processing products, i.e. the truncated version of galectin-3 and the N-terminal domains of galectin-4, -8 and -9, were performed. Normal healthy donors (p, n = 20; c, n = 21) and patients with paraproteins (c, n = 19) served as controls. Highly significant optical density-value readings for IgG autoantibodies were consistently detected for the proto-type galectin-7 (SLE) and the tandem repeat-type galectin-8 and -9 (SLE and RA). Their presence was independent from the autoantibody status against double-stranded DNA (for patients with SLE) or a rheumatoid factor (for patients with RA), respectively. Importantly, anti-galectin-2 autoantibodies highly significantly correlated with the appearance of a secondary APS in patients with SLE so that this parameter may serve as an additional biomarker for APS. Equally of note, the presence of IgG autoantibodies against galectins capable to act as an opsonin may contribute to a sustained immune dysregulation in patients with chronic inflammatory rheumatic diseases. © The Author 2012. Published by Oxford University Press. All rights reserved.
CRIS-Team Scopus Importer:2021-02-03
Keywords: antiphospholipid syndrome; autoantibodies; galectins; systemic lupus erythematosus

Biocompatibility of Dextran-Coated 30 nm and 80 nm Sized SPIONs towards Monocytes, Dendritic Cells and Lymphocytes - Zschiesche, Lisa; Janko, Christina; Friedrich, Bernhard; Frey, Benjamin; Band, Julia; Lyer, Stefan; Alexiou, Christoph; Unterweger, Harald (Nanomaterials, 2023)
Dextran-coated superparamagnetic iron oxide nanoparticles (SPIONDex) of various sizes can be used as contrast agents in magnetic resonance imaging (MRI) of different tissues, e.g., liver or atherosclerotic plaques, after intravenous injection. In previous studies, the blood compatibility and the absence of immunogenicity of SPIONDex was demonstrated. The investigation of the interference of SPIONDex with stimulated immune cell activation is the aim of this study. For this purpose, sterile and endotoxin-free SPIONDex with different hydrodynamic sizes (30 and 80 nm) were investigated for their effect on monocytes, dendritic cells (DC) and lymphocytes in concentrations up to 200 µg/mL, which would be administered for use as an imaging agent. The cells were analyzed using flow cytometry and brightfield microscopy. We found that SPIONDex were hardly taken up by THP-1 monocytes and did not reduce cell viability. In the presence of SPIONDex, the phagocytosis of zymosan and E. coli by THP-1 was dose-dependently reduced. SPIONDex neither induced the maturation of DCs nor interfered with their stimulated maturation. The particles did not induce lymphocyte proliferation or interfere with lymphocyte proliferation after stimulation. Since SPIONDex rapidly distribute via the blood circulation in vivo, high concentrations were only reached locally at the injection site immediately after application and only for a very limited time. Thus, SPIONDex can be considered immune compatible in doses required for use as an MRI contrast agent.
CRIS-Team Scopus Importer:2023-01-20
Keywords: biocompatibility; immune response; magnetic resonance imaging (MRI); nanomedicine; superparamagnetic iron oxide nanoparticles (SPION)

Calpain-1 weakens the nuclear envelope and promotes the release of neutrophil extracellular traps - Singh, Jeeshan; Zlatar, Leticija; Munoz Becerra, Marco; Lochnit, Günter; Herrmann, Irmgard; Pfister, Felix; Janko, Christina; Knopf, Jasmin; Leppkes, Moritz; Schoen, Janina; Munoz, Luis Enrique; Schett, Georg; et al. (Cell Communication and Signaling, 2024)
The inducers of neutrophil extracellular trap (NET) formation are heterogeneous and consequently, there is no specific pathway or signature molecule indispensable for NET formation. But certain events such as histone modification, chromatin decondensation, nuclear envelope breakdown, and NET release are ubiquitous. During NET formation, neutrophils drastically rearrange their cytoplasmic, granular and nuclear content. Yet, the exact mechanism for decoding each step during NET formation still remains elusive. Here, we investigated the mechanism of nuclear envelope breakdown during NET formation. Immunofluorescence microscopic evaluation revealed a gradual disintegration of outer nuclear membrane protein nesprin-1 and alterations in nuclear morphology during NET formation. MALDI-TOF analysis of NETs that had been generated by various inducers detected the accumulation of nesprin-1 fragments. This suggests that nesprin-1 degradation occurs before NET release. In the presence of a calpain-1, inhibitor nesprin-1 degradation was decreased in calcium driven NET formation. Microscopic evaluation confirmed that the disintegration of the lamin B receptor (LBR) and the collapse of the actin cytoskeleton occurs in early and later phases of NET release, respectively. We conclude that the calpain-1 degrades nesprin-1, orchestrates the weakening of the nuclear membrane, contributes to LBR disintegration, and promoting DNA release and finally, NETs formation.
CRIS-Team Scopus Importer:2024-09-20
Keywords: Calpain-1; Nesprin-1; Neutrophil extracellular traps (NETs); Nuclear envelope break down

Cellular effects of paclitaxel-loaded iron oxide nanoparticles on breast cancer using different 2D and 3D cell culture models - Lugert, Stephan; Unterweger, Harald; Mühlberger, Marina; Janko, Christina; Janko, Christina; Draack, Sebastian; Ludwig, Frank; Eberbeck, Dietmar; Alexiou, Christoph; Friedrich, Ralf P. (International Journal of Nanomedicine, 2019)
Background: Magnetic drug targeting (MDT) is an effective alternative for common drug applications, which reduces the systemic drug load and maximizes the effect of, eg, chemotherapeutics at the site of interest. After the conjugation of a magnetic carrier to a chemotherapeutic agent, the intra-arterial injection into a tumor-afferent artery in the presence of an external magnetic field ensures the accumulation of the drug within the tumor tissue. Materials and methods: In this study, we used superparamagnetic iron oxide nanoparticles (SPIONs) coated with lauric acid and human serum albumin as carriers for paclitaxel (SPIONLA-HSA-Ptx). To investigate whether this particle system is suitable for a potential treatment of cancer, we investigated its physicochemical properties by dynamic light scattering, ζ potential measurements, isoelectric point titration, infrared spectroscopy, drug release quantification, and magnetic susceptibility measurements. The cytotoxic effects were evaluated using extensive toxicological methods using flow cytometry, IncuCyte® live-cell imaging, and growth experiments on different human breast cancer cell lines in two- and three-dimensional cell cultures. Conclusion: The data showed that next to their high magnetization capability, SPIONLA-HSA-Ptx have similar cytostatic effects on human breast cancer cells as pure paclitaxel, suggesting their usage for future MDT-based cancer therapy.
EVALuna2:35447

Cell Viability and Immunogenic Function of T Cells Loaded with Nanoparticles for Spatial Guidance in Magnetic Fields - Pfister, Felix; Alexiou, Christoph; Janko, Christina (Humana Press Inc., 2023)
Immune cell therapies, such as adoptive T cell therapies, are an innovative and powerful treatment option for previously non-treatable diseases. Although immune cell therapies are thought to be very specific, there is still the danger of developing severe to life-threatening side effects due to the unspecific distribution of the cells throughout the body (on-target/off-tumor effects). A possible solution for the reduction of these side effects and the improvement of tumor infiltration is the specific targeting of the effector cells (e.g., T cells) to the desired destination (e.g., tumor region). This can be achieved by the magnetization of cells with superparamagnetic iron oxide nanoparticles (SPIONs) for spatial guidance via external magnetic fields. A prerequisite for the use of SPION-loaded T cells in adoptive T cell therapies is that cell viability and functionality after nanoparticle loading are preserved. Here, we demonstrate a protocol to analyze cell viability and functionality such as activation, proliferation, cytokine release, and differentiation at a single cell level using flow cytometry.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Cell viability; Flow cytometry; Intracellular cytokine staining; T cells; T cell activation; T cell proliferation

Characterizations of drug carrying magnetic nanoparticles for tumor therapy: Biological outcome and first immunological aspects - Dürr, Stephan; Tietze, Rainer; Lyer, Stefan; Janko, Christina; Schreiber, Eveline; Mann, Johannes; Turcu, R.; Gitter, K.; Odenbach, S.; Vasylyev, Serhiy; Herrmann, Martin; Peukert, Wolfgang; et al. (Magnetohydrodynamics, 2013)
Nanosized magnetic drug carriers offer a splendid prospect for directed drug application. The increased drug concentration in cancer tissue reached for this kind of application enables therapeutic effects on tumors that cannot be achieved using conventional chemotherapeutic treatment. Characterizing the drug targeting system and its behavior in vitro is necessary for understanding the biological outcome. In our studies, IRspectroscopy shows covalent binding of the biocompatible fatty acid layer. Although binding of mitoxantrone (MTO) to particles is hardly defined, considerable amounts of drug can be carried by nanoparticles. Furthermore, the nanosized drug carrier complex has to be investigated due to its biological outcome. Real-time cell analysis is useful to observe the therapeutic particles concerning their outcome in cell culture time-resolved up to several days. First experiments in concordance to a conventional assay show that the effectivity of nanoparticle bound MTO in cell culture is higher than treatment with pure MTO. A preliminary study demonstrates that the burden of the immune system is reduced by Magnetic Drug Targeting (MDT) vs. conventional chemotherapy. For a better understanding of MDT for cancer treatment, further studies have to be done to explain especially the binding behavior of superparamagnetic iron oxide nanoparticles to the respective chemotherapeutic agent.
Keywords: nano; magnetic; characterization; particle; agent

Citrate-coated superparamagnetic iron oxide nanoparticles enable a stable non-spilling loading of t cells and their magnetic accumulation - Boosz, Philipp; Pfister, Felix; Stein, René; Friedrich, Bernhard; Fester, Lars; Band, Julia; Mühlberger, Marina; Schreiber, Eveline; Lyer, Stefan; Dudziak, Diana; Alexiou, Christoph; Janko, Christina (Cancers, 2021)
T cell infiltration into a tumor is associated with a good clinical prognosis of the patient and adoptive T cell therapy can increase anti-tumor immune responses. However, immune cells are often excluded from tumor infiltration and can lack activation due to the immune-suppressive tumor microenvironment. To make T cells controllable by external forces, we loaded primary human CD3+ T cells with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONs). Since the efficacy of magnetic targeting depends on the amount of SPION loading, we investigated how experimental conditions influence nanoparticle uptake and viability of cells. We found that loading in the presence of serum improved both the colloidal stability of SPIONs and viability of T cells, whereas stimulation with CD3/CD28/CD2 and IL-2 did not influence nanoparticle uptake. Further-more, SPION loading did not impair cytokine secretion after polyclonal stimulation. We finally achieved 1.4 pg iron loading per cell, which was both located intracellularly in vesicles and bound to the plasma membrane. Importantly, nanoparticles did not spill over to non-loaded cells. Since SPION-loading enabled efficient magnetic accumulation of T cells in vitro under dynamic condi-tions, we conclude that this might be a good starting point for the investigation of in vivo delivery of immune cells.
CRIS-Team Scopus Importer:2021-09-03
Keywords: Adoptive T cell transfer; Immune therapy; Magnetic targeting; Nanomedicine; Solid tumor; Superparamagnetic iron oxide nanoparticles (SPIONs); Targeted transport

Comparative in vitro and in vivo Evaluation of Different Iron Oxide-Based Contrast Agents to Promote Clinical Translation in Compliance with Patient Safety - Unterweger, Harald; Janko, Christina; Folk, Tamara; Cicha, Iwona; Kovacs, Noemi; Gyebnar, Gyula; Horvath, Ildiko; Mathe, Domokos; Zheng, Kang H.; Coolen, Bram F.; Stroes, Erik; Szebeni, Janos; et al. (International Journal of Nanomedicine, 2023)
Introduction: One of the major challenges in the clinical translation of nanoparticles is the development of formulations combining favorable efficacy and optimal safety. In the past, iron oxide nanoparticles have been introduced as an alternative for gadolinium-containing contrast agents; however, candidates available at the time were not free from adverse effects. Methods: Following the development of a potent iron oxide-based contrast agent SPIONDex, we now performed a systematic comparison of this formulation with the conventional contrast agent ferucarbotran and with ferumoxytol, taking into consideration their physicochemical characteristics, bio-and hemocompatibility in vitro and in vivo, as well as their liver imaging properties in rats. Results: The results demonstrated superior in vitro cyto-, hemo-and immunocompatibility of SPIONDex in comparison to the other two formulations. Intravenous administration of ferucarbotran or ferumoxytol induced strong complement activation-related pseu-doallergy in pigs. In contrast, SPIONDex did not elicit any hypersensitivity reactions in the experimental animals. In a rat model, comparable liver imaging properties, but a faster clearance was demonstrated for SPIONDex. Conclusion: The results indicate that SPIONDex possess an exceptional safety compared to the other two formulations, making them a promising candidate for further clinical translation.
CRIS-Team Scopus Importer:2023-05-26
Keywords: CARPA; complement activation; magnetic resonance imaging; MRI; nanomedicine; nanoparticles

Development and characterization of magnetic iron oxide nanoparticles with a cisplatin-bearing polymer coating for targeted drug delivery - Unterweger, Harald; Tietze, Rainer; Janko, Christina; Zaloga, Jan; Lyer, Stefan; Dürr, Stephan; Taccardi, Nicola; Goudouri, Ourania Menti; Hoppe, Alexander; Eberbeck, Dietmar; Schubert, Dirk W.; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2014)
A highly selective and efficient cancer therapy can be achieved using magnetically directed superparamagnetic iron oxide nanoparticles (SPIONs) bearing a sufficient amount of the therapeutic agent. In this project, SPIONs with a dextran and cisplatin-bearing hyaluronic acid coating were successfully synthesized as a novel cisplatin drug delivery system. Transmission electron microscopy images as well as X-ray diffraction analysis showed that the individual magnetite particles were around 4.5 nm in size and monocrystalline. The small crystallite sizes led to the superparamagnetic behavior of the particles, which was exemplified in their magnetization curves, acquired using superconducting quantum interference device measurements. Hyaluronic acid was bound to the initially dextran-coated SPIONs by esterification. The resulting amide bond linkage was verified using Fourier transform infrared spectroscopy. The additional polymer layer increased the vehicle size from 22 nm to 56 nm, with a hyaluronic acid to dextran to magnetite weight ratio of 51:29:20. A maximum payload of 330 μg cisplatin/mL nanoparticle suspension was achieved, thus the particle size was further increased to around 77 nm with a zeta potential of -45 mV. No signs of particle precipitation were observed over a period of at least 8 weeks. Analysis of drug-release kinetics using the dialysis tube method revealed that these were driven by inverse ligand substitution and diffusion through the polymer shell as well as enzymatic degradation of hyaluronic acid. The biological activity of the particles was investigated in a nonadherent Jurkat cell line using flow cytometry. Further, cell viability and proliferation was examined in an adherent PC-3 cell line using xCELLigence analysis. Both tests demonstrated that particles without cisplatin were biocompatible with these cells, whereas particles with the drug induced apoptosis in a dose-dependent manner, with secondary necrosis after prolonged incubation. In conclusion, combination of dextran-coated SPIONs with hyaluronic acid and cisplatin represents a promising approach for magnetic drug targeting in the treatment of cancer.

Dextran-coated superparamagnetic iron oxide nanoparticles for magnetic resonance imaging: Evaluation of size-dependent imaging properties, storage stability and safety - Unterweger, Harald; Dezsi, Laszlo; Matuszak, Jasmin; Janko, Christina; Poettler, Marina; Jordan, Jutta; Bäuerle, Tobias; Szebeni, Janos; Fey, Tobias; Boccaccini, Aldo R.; Alexiou, Christoph; Cicha, Iwona (International Journal of Nanomedicine, 2018)
Keywords: Irritation potential; Cross-linking; CARPA; Storage stability; SPION; MRI

Different storage conditions influence biocompatibility and physicochemical properties of iron oxide nanoparticles - Zaloga, Jan; Janko, Christina; Agarwal, Rohit; Nowak, Johannes; Müller, Robert; Boccaccini, Aldo R.; Lee, Geoffrey; Odenbach, Stefan; Lyer, Stefan; Alexiou, Christoph (International Journal of Molecular Sciences, 2015)
Superparamagnetic iron oxide nanoparticles (SPIONs) have attracted increasing attention in many biomedical fields. In magnetic drug targeting SPIONs are injected into a tumour supplying artery and accumulated inside the tumour with a magnet. The effectiveness of this therapy is thus dependent on magnetic properties, stability and biocompatibility of the particles. A good knowledge of the effect of storage conditions on those parameters is of utmost importance for the translation of the therapy concept into the clinic and for reproducibility in preclinical studies. Here, core shell SPIONs with a hybrid coating consisting of lauric acid and albumin were stored at different temperatures from 4 to 45 °C over twelve weeks and periodically tested for their physicochemical properties over time. Surprisingly, even at the highest storage temperature we did not observe denaturation of the protein or colloidal instability. However, the saturation magnetisation decreased by maximally 28.8% with clear correlation to time and storage temperature. Furthermore, the biocompatibility was clearly affected, as cellular uptake of the SPIONs into human T-lymphoma cells was crucially dependent on the storage conditions. Taken together, the results show that the particle properties undergo significant changes over time depending on the way they are stored.
Keywords: Colloidal stability; Iron oxide biocompatibility; Iron oxide nanoparticles; Magnetic drug targeting; Magnetite maghemite biocompatibility; Nanomedicine; Nanoparticle stability

Effect of BSA-coated Superparamagnetic Iron Oxide Nanoparticles on Granulosa Cells - Poettler, Marina; Hofmann, Simone; Dürr, Stephan; Unterweger, Harald; Wiest, Irmi; Zaloga, Jan; Alexiou, Christoph; Jeschke, Udo; Janko, Christina (Anticancer Research, 2016)
Since superparamagnetic iron oxide nanoparticles (SPION) possess unique features, they provide a huge platform for medical applications, especially for cancer diagnosis and therapy (e.g. imaging, and drug targeting). However, heterogeneous effects on mammalian cells with regard to reproductive tissue are described. An experimental study was carried out to study the effects of SPIONs on both the expression of steroid hormone receptor and viability of granulosa cells, which play a key role in ovarian health and fertility.Human granulosa cells were cultured in vitro and incubated with different concentrations of SPIONs. After 48 h, steroid receptor expression and cell viability were evaluated.Treatment of granulosa cells with SPIONs did not affect estrogen receptor ?1 or progesterone receptor-A expression and had no significant effect on cell viability.Nanoparticles precoated with bovine serum albumin (BSA) do not alter granulosa cell phenotype, whereas literature suggests that other nanoparticles induce apoptosis and reduce steroid receptor expression. Our data indicate an overall better outcome using SPIONs coated with BSA.
EVALuna2:20012

Elevated Serum Lysophosphatidylcholine in Patients with Systemic Lupus Erythematosus Impairs Phagocytosis of Necrotic Cells In Vitro - Grossmayer, Gerhard E.; Keppeler, Hildegard; Boeltz, Sebastian; Janko, Christina; Rech, Jürgen; Herrmann, Martin; Lauber, Kirsten; Munoz, Luis Enrique; Munoz Becerra, Luis (Frontiers in Immunology, 2017)
Impaired clearance of dying and dead cells by professional and amateur phagocytes plays a crucial role in the etiology of systemic lupus erythematosus (SLE). While dying, cells expose and release a plethora of eat-me and find-me signals to ensure their timely removal before entering the dangerous stage of secondary necrosis. A well-described chemoattractant for macrophages is dying cell-derived lysophosphatidylcholine (LPC). However, its implications for and/or its association with SLE disease, so far, have not been examined. In the present study, we analyzed the LPC serum concentrations of patients with SLE and rheumatoid arthritis (RA). Subsequently, we examined if and to which extent the measured serum concentrations of LPC and an LPC-rich environment can impact the phagocytosis of necrotic cells.Sera from patients with SLE, RA, and normal healthy donors (NHD) were characterized for several parameters, including LPC concentrations. Phagocytosis of dead cells by human macrophages in the presence of SLE and NHD sera was quantified. Additionally, the impact of exogenously added, purified LPC on phagocytosis was analyzed.Patients with SLE had significantly increased LPC serum levels, and high serum LPC of SLE patients correlated significantly with impaired phagocytosis of dead cells in the presence of heat-inactivated serum. Phagocytosis in the presence of sera from NHD showed no correlation to LPC levels, but exogenous addition of purified LPC in the range as measured in SLE patients' sera led to a concentration-dependent decrease.Our data show that high levels of LPC as observed in the sera of SLE patients have a negative impact on the clearance of dead cells by macrophages. Chemoattraction requires a concentration gradient. The higher the LPC concentration surrounding a dying or dead cell, the smaller the achievable gradient upon LPC release will be. Thus, it is feasible to assume that elevated LPC levels can interfere with the build-up of a local LPC gradient during cell death, and hence might play a role in the establishment and/or perpetuation of SLE disease.
EVALuna2:13530

Elevated serum lysophosphatidylcholine in patients with systemic lupus erythematosus impairs phagocytosis of necrotic cells in vitro - Grossmayer, Gerhard E.; Keppeler, Hildegard; Böltz, Sebastian; Janko, Christina; Rech, Jürgen; Herrmann, Martin; Lauber, Kirsten; Munoz, Luis Enrique (Frontiers in Immunology, 2018)
Keywords: Lysophosphatidylcholine; Necrotic cells; Clearance deficiency; Efferocytosis; Serum; Systemic lupus erythematosus; Phagocytosis; Rheumatoid arthritis

Facile preparation of multifunctional superparamagnetic PHBV microspheres containing SPIONs for biomedical applications - Li, Wei; Zaloga, Jan; Ding, Yaping; Liu, Yufang; Janko, Christina; Pischetsrieder, Monika; Alexiou, Christoph; Boccaccini, Aldo R. (Scientific Reports, 2016)
The promising potential of magnetic polymer microspheres in various biomedical applications has been frequently reported. However, the surface hydrophilicity of superparamagnetic iron oxide nanoparticles (SPIONs) usually leads to poor or even failed encapsulation of SPIONs in hydrophobic polymer microspheres using the emulsion method. In this study, the stability of SPIONs in poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) solution was significantly increased after surface modification with lauric acid. As a result, magnetic PHBV microspheres with high encapsulation efficiencies (71.0-87.4%) were prepared using emulsion-solvent extraction/evaporation method. Magnetic resonance imaging (MRI) showed significant contrast for the magnetic PHBV microspheres. The toxicity of these magnetic PHBV microspheres towards human T-lymphoma suspension cells and adherent colon carcinoma HT-29 cells was investigated using flow cytometry, and they were shown to be non-toxic in a broad concentration range. A model drug, tetracycline hydrochloride, was used to demonstrate the drug delivery capability and to investigate the drug release behavior of the magnetic PHBV microspheres. The drug was successfully loaded into the microspheres using lauric acid-coated SPIONs as drug carrier, and was released from the microspheres in a diffusion controlled manner. The developed magnetic PHBV microspheres are promising candidates for biomedical applications such as targeted drug delivery and MRI.

Functionalization of T lymphocytes for magnetically controlled immune therapy: Selection of suitable superparamagnetic iron oxide nanoparticles - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Schreiber, Eveline; Band, Julia; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Magnetism and Magnetic Materials, 2019)
According to the World Health Organization, cancer is the second most important cause of death in Europe. Due to its manifold manifestations, it is not possible to treat all patients according to a uniform scheme. However, all solid tumors have one thing in common: independent of the tumor's molecular subgroup and the treatment protocol, the immune status of the tumor, especially the amount of tumor infiltrating lymphocytes (TILs), is important for the patient's clinical outcome - the higher the number of TILs, the better the outcome. For this reason it seems desirable to increase the number of TILs. One way to accumulate T cells in the tumor area is to make them magnetizable and attract them with an external magnetic field. Magnetization can be achieved by superparamagnetic iron oxide nanoparticles (SPIONs) which can be bound to the cells' surface or internalized into the cells. For this study, SPIONs with different coatings were synthesized and incubated with immortalized mouse T lymphocytes. SPIONs only stabilized with lauric acid (LA) coated in situ or afterwards showed high toxicity. Addition of an albumin layer increased the biocompatibility but reduced cellular uptake. To increase the cellular uptake the albumin coated particles were aminated, leading to both higher uptake and toxicity, dependent on the degree of amination. In the presence of an externally applied magnetic field, T cells loaded with selected types and amounts of SPIONs were guidable. With this promising pilot study we already can demonstrate that it is possible to attract SPION bearing T cells by an external magnet. To sum up, biocompatibility and uptake of SPIONs by T cells are opposing events. Thus, for the functionalization of T cells with SPIONs the balance between uptake and toxicity must be evaluated carefully.
EVALuna2:35445

Functionalization Of T Lymphocytes With Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles For Magnetically Controlled Immune Therapy - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Friedrich, Ralf P.; Friedrich, Bernhard; Band, Julia; Cebulla, Nadine; Alexiou, Christoph; Dudziak, Diana; Lee, Geoffrey; Tietze, Rainer (International Journal of Nanomedicine, 2019)
Purpose: Immune activation with T cell tumor infiltration is beneficial for the prognosis of patients suffering from solid cancer. Depending on their immune status, solid tumors can be immunologically classified into three groups: "hot" tumors are infiltrated with T lymphocytes, "cold" tumors are not infiltrated and "immune excluded" tumors are only infiltrated in the peripheral tumor tissue. Checkpoint inhibitors provide new therapeutic options for "hot" tumors by triggering the immune response of T cells. In order to enable this for cold tumors as well, T cells must be enriched in the tumor. Therefore, we use the principle of magnetic targeting to guide T cells loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate) to the tumor by an externally applied magnetic field. Methods: SPIONCitrate were produced by alkaline coprecipitation of iron(II) and iron(III) chloride and in situ coating with sodium citrate. The concentration-dependent cytocompatibility of the particles was determined by flow cytometry and blood stability assays. Atomic emission spectroscopy was used for the quantification of the particle uptake into T lymphocytes. The attractability of the loaded cells was observed by live-cell imaging in the presence of an externally applied magnetic field. Results: SPIONCitrate displayed good cytocompatibility to T cells and did not show any sign of aggregation in blood. Finally, SPIONCitrate-loaded T cells were strongly attracted by a small external magnet. Conclusion: T cells can be "magnetized" by incorporation of SPIONCitrate for magnetic targeting. The production of the particle-cell hybrid system is straightforward, as the loading process only requires basic laboratory devices and the loading efficiency is sufficient for cells being magnetically controllable. For these reasons, SPIONCitrate are potential suitable candidates for magnetic T cell targeting.
EVALuna2:209938

Functionalized Superparamagnetic Iron Oxide Nanoparticles (SPIONs) as Platform for the Targeted Multimodal Tumor Therapy - Janko, Christina; Ratschker, Teresa; Nguyen, Khanh; Zschiesche, Lisa; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Frontiers in Oncology, 2019)
Standard cancer treatments involve surgery, radiotherapy, chemotherapy, and immunotherapy. In clinical practice, the respective drugs are applied orally or intravenously leading to their systemic circulation in the whole organism. For chemotherapeutics or immune modulatory agents, severe side effects such as immune depression or autoimmunity can occur. At the same time the intratumoral drug doses are often too low for effective cancer therapy. Since monotherapies frequently cannot cure cancer, due to their synergistic effects multimodal therapy concepts are applied to enhance treatment efficacy. The targeted delivery of drugs to the tumor by employment of functionalized nanoparticles might be a promising solution to overcome these challenges. For multimodal therapy concepts and individualized patient care nanoparticle platforms can be functionalized with compounds from various therapeutic classes (e.g. radiosensitizers, phototoxic drugs, chemotherapeutics, immune modulators). Superparamagnetic iron oxide nanoparticles (SPIONs) as drug transporters can add further functionalities, such as guidance or heating by external magnetic fields (Magnetic Drug Targeting or Magnetic Hyperthermia), and imaging-controlled therapy (Magnetic Resonance Imaging).
CRIS-Team WoS Importer:2019-02-27

Genotoxicity of Superparamagnetic Iron Oxide Nanoparticles in Granulosa Cells - Poettler, Marina; Staicu, Andreas; Zaloga, Jan; Unterweger, Harald; Weigel, Bianca; Schreiber, Eveline; Hofmann, Simone; Wiest, Irmi; Jeschke, Udo; Alexiou, Christoph; Janko, Christina (International Journal of Molecular Sciences, 2015)
Nanoparticles that are aimed at targeting cancer cells, but sparing healthy tissue provide an attractive platform of implementation for hyperthermia or as carriers of chemotherapeutics. According to the literature, diverse effects of nanoparticles relating to mammalian reproductive tissue are described. To address the impact of nanoparticles on cyto- and genotoxicity concerning the reproductive system, we examined the effect of superparamagnetic iron oxide nanoparticles (SPIONs) on granulosa cells, which are very important for ovarian function and female fertility. Human granulosa cells (HLG-5) were treated with SPIONs, either coated with lauric acid (SEONLA) only, or additionally with a protein corona of bovine serum albumin (BSA; SEON(LA-BSA)), or with dextran (SEON(DEX)). Both micronuclei testing and the detection of ?H2A.X revealed no genotoxic effects of SEON(LA-BSA), SEON(DEX) or SEON(LA). Thus, it was demonstrated that different coatings of SPIONs improve biocompatibility, especially in terms of genotoxicity towards cells of the reproductive system.
EVALuna2:19986

Graphene-Induced Hyperthermia (GIHT) Combined With Radiotherapy Fosters Immunogenic Cell Death - Podolska, Malgorzata; Shan, Xiaomei; Janko, Christina; Boukherroub, Rabah; Gaipl, Udo; Szunerits, Sabine; Frey, Benjamin; Munoz, Luis Enrique (Frontiers in Oncology, 2021)
Radiotherapy and chemotherapy are the standard interventions for cancer patients, although cancer cells often develop radio- and/or chemoresistance. Hyperthermia reduces tumor resistance and induces immune responses resulting in a better prognosis. We have previously described a method to induce tumor cell death by local hyperthermia employing pegylated reduced graphene oxide nanosheets and near infrared light (graphene-induced hyperthermia, GIHT). The spatiotemporal exposure/release of heat shock proteins (HSP), high group mobility box 1 protein (HMGB1), and adenosine triphosphate (ATP) are reported key inducers of immunogenic cell death (ICD). We hypothesize that GIHT decisively contributes to induce ICD in irradiated melanoma B16F10 cells, especially in combination with radiotherapy. Therefore, we investigated the immunogenicity of GIHT alone or in combination with radiotherapy in melanoma B16F10 cells. Tumor cell death in vitro revealed features of apoptosis that is progressing fast into secondary necrosis. Both HSP70 and HMGB1/DNA complexes were detected 18 hours post GIHT treatment, whereas the simultaneous release of ATP and HMGB1/DNA was observed only 24 hours post combined treatment. We further confirmed the adjuvant potential of these released DAMPs by immunization/challenge experiments. The inoculation of supernatants of cells exposed to sole GIHT resulted in tumor growth at the site of inoculation. The immunization with cells exposed to sole radiotherapy rather fostered the growth of secondary tumors in vivo. Contrarily, a discreet reduction of secondary tumor volumes was observed in mice immunized with a single dose of cells and supernatants treated with the combination of GIHT and irradiation. We propose the simultaneous release of several DAMPs as a potential mechanism fostering anti-tumor immunity against previously irradiated cancer cells.
CRIS-Team Scopus Importer:2021-09-17
Keywords: hyperthermia; immunogenic cell death; melanoma; multimodal; radiotherapy; reduced graphene oxide

Graphene Oxide Nanosheets for Localized Hyperthermia-Physicochemical Characterization, Biocompatibility, and Induction of Tumor Cell Death - Podolska, Malgorzata; Barras, Alexandre; Alexiou, Christoph; Frey, Benjamin; Gaipl, Udo; Boukherroub, Rabah; Szunerits, Sabine; Janko, Christina; Munoz, Luis Enrique (Cells, 2020)
Background: The main goals of cancer treatment are not only to eradicate the tumor itself but also to elicit a specific immune response that overcomes the resistance of tumor cells against chemo- and radiotherapies. Hyperthermia was demonstrated to chemo- and radio-sensitize cancerous cells. Many reports have confirmed the immunostimulatory effect of such multi-modal routines. Methods: We evaluated the interaction of graphene oxide (GO) nanosheets; its derivatives reduced GO and PEGylated rGO, with components of peripheral blood and evaluated its thermal conductivity to induce cell death by localized hyperthermia. Results: We confirmed the sterility and biocompatibility of the graphene nanomaterials and demonstrated that hyperthermia applied alone or in the combination with radiotherapy induced much more cell death in tumor cells than irradiation alone. Cell death was confirmed by the release of lactate dehydrogenase from dead and dying tumor cells. Conclusion: Biocompatible GO and its derivatives can be successfully used in graphene-induced hyperthermia to elicit tumor cell death.
CRIS-Team WoS Importer:2020-05-15

Highlights from the latest articles in nanoparticles, nanomaterials and nanotoxicity testing - Lyer, Stefan; Cicha, Iwona; Friedrich, Ralf; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2015)
EVALuna2:19966

Human T cells loaded with superparamagnetic iron oxide nanoparticles retain antigen-specific TCR functionality. - Pfister, Felix; Dörrie, Jan; Schaft, Niels; Buchele, Vera; Unterweger, Harald; Carnell, Lucas R.; Schreier, Patrick; Stein, René; Kubánková, Markéta; Guck, Jochen; Hackstein, Holger; Alexiou, Christoph; et al. (Frontiers in Immunology, 2023)
BACKGROUND: Immunotherapy of cancer is an emerging field with the potential to improve long-term survival. Thus far, adoptive transfer of tumor-specific T cells represents an effective treatment option for tumors of the hematological system such as lymphoma, leukemia or myeloma. However, in solid tumors, treatment efficacy is low owing to the immunosuppressive microenvironment, on-target/off-tumor toxicity, limited extravasation out of the blood vessel, or ineffective trafficking of T cells into the tumor region. Superparamagnetic iron oxide nanoparticles (SPIONs) can make cells magnetically controllable for the site-specific enrichment. METHODS: In this study, we investigated the influence of SPION-loading on primary human T cells for the magnetically targeted adoptive T cell therapy. For this, we analyzed cellular mechanics and the T cell response after stimulation via an exogenous T cell receptor (TCR) specific for the melanoma antigen MelanA or the endogenous TCR specific for the cytomegalovirus antigen pp65 and compared them to T cells that had not received SPIONs. RESULTS: SPION-loading of human T cells showed no influence on cellular mechanics, therefore retaining their ability to deform to external pressure. Additionally, SPION-loading did not impair the T cell proliferation, expression of activation markers, cytokine secretion, and tumor cell killing after antigen-specific activation mediated by the TCR. CONCLUSION: In summary, we demonstrated that SPION-loading of T cells did not affect cellular mechanics or the functionality of the endogenous or an exogenous TCR, which allows future approaches using SPIONs for the magnetically enrichment of T cells in solid tumors.
EVALuna2:539766
Keywords: Adoptive T cell therapy; superparamagnetic iron oxide nanoparticles (SPIONs); antigen-specific T cell response; targeted immune therapy; cell deformability

Hypericin-bearing magnetic iron oxide nanoparticles for selective drug delivery in photodynamic therapy - Unterweger, Harald; Subatzus, Daniel; Tietze, Rainer; Janko, Christina; Poettler, Marina; Stiegelschmitt, Alfons; Schuster, Matthias; Maake, Caroline; Boccaccini, Aldo R.; Alexiou, Christoph (International Journal of Nanomedicine, 2015)
Combining the concept of magnetic drug targeting and photodynamic therapy is a promising approach for the treatment of cancer. A high selectivity as well as significant fewer side effects can be achieved by this method, since the therapeutic treatment only takes place in the area where accumulation of the particles by an external electromagnet and radiation by a laser system overlap. In this article, a novel hypericin-bearing drug delivery system has been developed by synthesis of superparamagnetic iron oxide nanoparticles (SPIONs) with a hypericin-linked functionalized dextran coating. For that, sterically stabilized dextran-coated SPIONs were produced by coprecipitation and crosslinking with epichlorohydrin to enhance stability. Carboxymethylation of the dextran shell provided a functionalized platform for linking hypericin via glutaraldehyde. Particle sizes obtained by dynamic light scattering were in a range of 55-85 nm, whereas investigation of single magnetite or maghemite particle diameter was performed by transmission electron microscopy and X-ray diffraction and resulted in approximately 4.5-5.0 nm. Surface chemistry of those particles was evaluated by Fourier transform infrared spectroscopy and ζ potential measurements, indicating successful functionalization and dispersal stabilization due to a mixture of steric and electrostatic repulsion. Flow cytometry revealed no toxicity of pure nanoparticles as well as hypericin without exposure to light on Jurkat T-cells, whereas the combination of hypericin, alone or loaded on particles, with light-induced cell death in a concentration and exposure time-dependent manner due to the generation of reactive oxygen species. In conclusion, the combination of SPIONs’ targeting abilities with hypericin’s phototoxic properties represents a promising approach for merging magnetic drug targeting with photodynamic therapy for the treatment of cancer.
Keywords: Hypericin; Magnetic drug targeting; Photodynamic therapy; SPION

Imaging modalities using magnetic nanoparticles - overview of the developments in recent years - Schwarz, Marc; Dörfler, Arnd; Engelhorn, Tobias; Struffert, Tobias; Tietze, Rainer; Janko, Christina; Tripal, Philipp; Cicha, Iwona; Dürr, Stephan; Alexiou, Christoph; Lyer, Stefan (Nanotechnology Reviews, 2013)
The use of nanoparticles in tumor imaging, molecular imaging, and drug delivery has significantly expanded in the last few years. The relatively new field of "theranostics" combines their capacity for drug delivery with their potential as contrast agents. Depending on the imaging modality used, several types of nanoparticles are available, such as gold for optical imaging or superparamagnetic iron oxide for magnetic resonance imaging. This review will give a short overview of the different types of nanoparticles as well as their development and potential application in recent years. Furthermore, it describes the research on classic imaging modalities as well as on new techniques to image nanoparticles in vivo and focuses on magnetic-based imaging modalities.
EVALuna2:19967

Immunohistochemical Evaluation of E6/E7 HPV Oncoproteins Staining in Cervical Cancer - Stiasny, Annika; Kuhn, Christina; Mayr, Doris; Alexiou, Christoph; Janko, Christina; Wiest, Irmi; Jeschke, Udo; Kost, Bernd (Anticancer Research, 2016)
High-risk human papillomavirus (HPV) subtypes (i.e. 16 and 18) lead to uterine cervical cancer as well as HPV-positive oropharyngeal cancer (OSCC), a form of head and neck cancer. The induction of HPV-induced cancer is driven by virus-specific oncoproteins E6 and E7. E6 protein of HPV types 16 and 18 interacts with the E3 ubiquitin protein ligase, resulting in ubiquitination and proteolysis of tumor protein p53. E7 inactivates retinoblastoma protein (Rb) by phosphorylation followed by an increase of free eukaryotic transcription factor E2F (E2F) in the cell. This leads to an increase of cyclin-dependent kinase inhibitor p16, that is used as an immunohistochemical marker of HPV-associated OSCC. Unfortunately, p16 is not exclusively increased by E7 oncoprotein in carcinogenesis. Therefore, the aim of this study was to develop an immunohistochemical approach for the direct detection of E6/E7 oncoproteins in uterine cervical cancer as well as in OSCC.Paraffin sections of uterine cervical cancer and 130 were analyzed. Immunohistochemical staining protocols were evaluated with tissue slides from patients with cervical dysplasia (CIN III) and squamous epithelial carcinoma tissue with HPV infection. Liver and placental tissues were used as negative controls. E6-Specific antibody (Biorbyt) was used as primary antibody. The polymer staining method and diaminobenzidine were applied for further development. Panels of E7-specific antibodies were tested. Again, the polymer staining method and diaminobenzidine were applied for further development.E6-Specific antibody revealed specific and intense staining after pre-incubation of tissue slides with citrate buffer solution. Only the E7 antibody obtained from Chemicon showed intense and specific staining in patients with CIN III and squamous epithelial carcinoma tissue. Pre-incubation with proteinase K diminished non-specific reaction.Our results revealed a useful staining protocol for the immunohistochemical evaluation of E6/E7 oncoprotein expression in uterine cervical cancer, as well as in HPV-positive oropharyngeal cancer. Advantages of this method compared to mRNA in situ hybridization of E6/E7 are the much lower costs, as well as the broader applicability in pathological practice.
EVALuna2:20013

Immunohistochemical Evaluation of the Role of p53 Mutation in Cervical Cancer: Ser-20 p53-Mutant Correlates with Better Prognosis - Freier, Christoph P.; Stiasny, Annika; Kuhn, Christina; Mayr, Doris; Alexiou, Christoph; Janko, Christina; Wiest, Irmi; Jeschke, Udo; Kost, Bernd (Anticancer Research, 2016)
Cervical cancer is driven by human papillomavirus virus-specific oncoprotein E6. E6 interacts with E3 ubiquitin-protein ligase, resulting in the proteolysis of p53 protein. The aim of this study was to analyze one TP53 mutation in patients with cervical cancer and to correlate it to prognosis.A total of 248 paraffin-embedded tumor samples were stained for mutated p53 protein. The distribution and intensity of staining both in the nucleus and cytoplasm were evaluated with a semi-quantitative immunohistochemical score.A total of 66% of studied cervical carcinomas expressed the mutated p53 protein. The overall survival was better for patients expressing the mutated p53 protein in the nucleus.Interestingly, we found a very high mutation rate of TP53 in a cancer type where p53 is initially inactivated via E6 during the development of cervical cancer. An unexpected finding is the correlation of this mutation with better survival, possibly due to better response to therapy.
EVALuna2:20011

Impact of Superparamagnetic Iron Oxide Nanoparticles on Vocal Fold Fibroblasts: Cell Behavior and Cellular Iron Kinetics - Poettler, Marina; Fliedner, Anna; Schreiber, Eveline; Janko, Christina; Friedrich, Ralf P.; Bohr, Christopher; Döllinger, Michael; Alexiou, Christoph; Dürr, Stephan (Nanoscale Research Letters, 2017)
PURPOSE: The voice is the most important instrument of communication. Tissue defects in the vocal fold (VF) area lead to serious reduction in quality of life, but thus far, no satisfactory VF implant exists. Therefore, we aim to establish a functional VF implant in a rabbit model by magnetic tissue engineering (MTE) using superparamagnetic iron oxide nanoparticles (SPION). Hence, iron quantification over time as well as cell behavior studies upon SPION treatment are of great importance. METHODS: Rabbit VF fibroblasts (VFF) were treated with different concentrations of SPIONs (20, 40, and 80 μg/cm2), and iron content was examined for up to 40 days using microwave plasma-atom emission spectroscopy. The effects of SPION treatment on VFF (adhesion, spreading, and migration), which are important for the formation of 3D structures, were tested. RESULTS: Cellular SPION quantification revealed that there was no residual iron remaining in VFFs after 40 days. SPIONs had a dose-dependent effect on cell adhesion, with good tolerability observed up to 20 μg/cm2. Migration and spreading were not significantly influenced by SPION treatment up to 80 μg/cm2. DISCUSSION AND CONCLUSION: To develop 3D structures, cell behavior should not be affected by SPION uptake. After 40 days, cells were free of iron as a result of metabolism or rarefication during cell division. Cell functions including adhesion, spreading, and migration were proven to be intact in a dose-dependent manner after SPION treatment, suggesting a safe usage of MTE for voice rehabilitation. Our results thus constitute a solid basis for a successful transfer of this technique into 3D constructs, in order to provide an individual and personalized human VF implant in the future.
EVALuna2:33203

Induction of immunogenic cell death by chemotherapeutics-loaded nanoparticles for targeted tumor therapy - Janko, Christina; Alev, Magdalena; Mühleisen, Laura; Weigel, B.; Zaloga, Jan; Alexiou, Christoph (2017)
EVALuna2:35460

Inefficient clearance of dying cells in patients with SLE: Anti-dsDNA autoantibodies, MFG-E8, HMGB-1 and other players - Kruse, Kristin; Janko, Christina; Urbonaviciute, Vilma; Mierke, Claudia T.; Winkler, Thomas; Voll, Reinhard E.; Schett, Georg; Munoz, Luis E.; Herrmann, Martin (Apoptosis, 2010)
Systemic lupus erythematosus (SLE) is a complex disease resulting from inflammatory responses of the immune system against several autoantigens. Inflammation is conditioned by the continuous presence of autoantibodies and leaked autoantigens, e.g. from not properly cleared dying and dead cells. Various soluble molecules and biophysical properties of the surface of apoptotic cells play significant roles in the appropriate recognition and further processing of dying and dead cells. We exemplarily discuss how Milk fat globule epidermal growth factor 8 (MFG-E8), biophysical membrane alterations, High mobility group box 1 (HMGB1), C-reactive protein (CRP), and anti-nuclear autoantibodies may contribute to the etiopathogenesis of the disease. Up to date knowledge about these key elements may provide new insights that lead to the development of new treatment strategies of the disease. © 2010 Springer Science+Business Media, LLC.
Keywords: ANA; Biophysical features; Clearance; CRP; HMGB-1; MFG-E8; Phosphatidylserine; Plasma membrane

Inert Coats of Magnetic Nanoparticles Prevent Formation of Occlusive Intravascular Co-aggregates With Neutrophil Extracellular Traps - Bilyy, Rostyslav; Unterweger, Harald; Weigel, Bianca; Dumych, Tetiana; Paryzhak, Solomiya; Vovk, Volodymyr; Liao, Ziyu; Alexiou, Christoph; Herrmann, Martin; Janko, Christina (Frontiers in Immunology, 2018)
If foreign particles enter the human body, the immune system offers several mechanisms of response. Neutrophils forming the first line of the immune defense either remove pathogens by phagocytosis, inactivate them by degranulation or release of reactive oxygen species or immobilize them by the release of chromatin decorated with the granular proteins from cytoplasm as neutrophil extracellular traps (NETs). Besides viable microbes like fungi, bacteria or viruses, also several sterile inorganic particles including nanoparticles reportedly activate NET formation. The physicochemical nanoparticle characteristics fostering NET formation are still elusive. Here we show that agglomerations of non-stabilized superparamagnetic iron oxide nanoparticles (SPIONs) induce NET formation by isolated human neutrophils, in whole blood experiments under static and dynamic conditions as well as in vivo. Stabilization of nanoparticles with biocompatible layers of either human serum albumin or dextran reduced agglomeration and NET formation by neutrophils. Importantly, this passivation of the SPIONs prevented vascular occlusions in vivo even when magnetically accumulated. We conclude that higher order structures formed during nanoparticle agglomeration primarily trigger NET formation and the formation of SPION-aggregated NET-co-aggregates, whereas colloid-disperse nanoparticles behave inert and are alternatively cleared by phagocytosis.
EVALuna2:35450

Innovative Toxicological Investigation Methods for Iron Oxide Nanoparticles in Nanomedicine - Janko, Christina; Pöttler, Marina; Matuszak, Jasmin; Unterweger, Harald; Hornung, Annkathrin; Friedrich, Ralf P.; Alexiou, Christoph (Chemie Ingenieur Technik, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) offer various possibilities for application in medicine. Comprehensive toxicological investigations based on proper physicochemical nanoparticle characterizations are a prerequisite for translation from bench to bedside. Since nanoparticles are prone to interfere with several classical toxicological readout systems, alternative methods are necessary. Multiparameter stainings for flow cytometry and fluorescence microscopy, label-free real-time cell analyses, 3D cell culture, and flow models will be discussed here.
EVALuna2:33180

Innovative toxikologische Untersuchungsmethoden für Eisenoxidnanopartikel in der Nanomedizin - Janko, Christina; Pottler, Marina; Matuszak, Jasmin; Unterweger, Harald; Hornung, Annkathrin; Friedrich, Ralf P.; Alexiou, Christoph (Chemie Ingenieur Technik, 2017)
Superparamagnetische Eisenoxidnanopartikel (SPIONs) bieten vielfältige Anwendungsmöglichkeiten in der Medizin. Toxikologische Untersuchungen, die auf der physikochemischen Charakterisierung der Nanopartikel aufbauen, sind eine wesentliche Voraussetzung für die zukünftige Translation in die klinische Anwendung. Da Nanopartikel mit zahlreichen klassischen toxikologischen Nachweismethoden interferieren, sind Alternativmethoden notwendig. Multiparameterfärbungen für Durchflusszytometrie und Fluoreszenzmikroskopie, markierungsfreie Echtzeitanalysen, 3D-Zellkultur und Flussmodelle werden diskutiert.
EAM Import::2019-03-13

Intracellular amplifiers of reactive oxygen species affecting mitochondria as radiosensitizers - Xu, Honggui; Reshetnikov, Viktor; Wondrak, Marit; Eckhardt, Lisa; Kunz-Schughart, Leoni A.; Janko, Christina; Tietze, Rainer; Alexiou, Christoph; Borchardt, Hannes; Aigner, Achim; Gong, Wenjie; Schmitt, Michael; et al. (Cancers, 2022)
Radiotherapy (RT) efficacy can be improved by using radiosensitizers, i.e., drugs enhancing the effect of ionizing radiation (IR). One of the side effects of RT includes damage of normal tissue in close proximity to the treated tumor. This problem can be solved by applying cancer specific radiosensitizers. N-Alkylaminoferrocene-based (NAAF) prodrugs produce reactive oxygen species (ROS) in cancer cells, but not in normal cells. Therefore, they can potentially act as cancer specific radiosensitizers. However, early NAAF prodrugs did not exhibit this property. Since functional mitochondria are important for RT resistance, we assumed that NAAF prodrugs affecting mitochondria in parallel with increasing intracellular ROS can potentially exhibit synergy with RT. We applied sequential Cu+-catalyzed alkyne-azide cycloadditions (CuAAC) to obtain a series of NAAF derivatives with the goal of improving anticancer efficacies over already existing com-pounds. One of the obtained prodrugs (2c) exhibited high anticancer activity with IC50 values in the range of 5–7.1 µM in human ovarian carcinoma, Burkitt’s lymphoma, pancreatic carcinoma and T-cell leukemia cells retained moderate water solubility and showed cancer specificity. 2c strongly affects mitochondria of cancer cells, leading to the amplification of mitochondrial and total ROS production and thus causing cell death via necrosis and apoptosis. We observed that 2c acts as a radiosensitizer in human head and neck squamous carcinoma cells. This is the first demonstration of a synergy between the radiotherapy and NAAF-based ROS amplifiers.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Cancer; Mitochondrion; N-alkylaminoferrocene; Prodrug; Radiotherapy; Reactive oxygen species

Intranasal delivery of nanoparticles - Friedrich, Ralf P.; Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2022)
CRIS-Team WoS Importer:2022-01-14

In Vitro Setup for Determination of Nanoparticle-Mediated Magnetic Cell and Drug Accumulation in Tumor Spheroids under Flow Conditions - Behr, Jessica; Carnell, Lucas R. R.; Stein, Rene; Pfister, Felix; Friedrich, Bernhard; Huber, Christian; Lyer, Stefan; Band, Julia; Schreiber, Eveline; Alexiou, Christoph; Janko, Christina (Cancers, 2022)
Simple Summary Magnetic nanoparticles can render therapeutics or drugs magnetically guidable, which enables their targeted transport to the diseased tissue in the patient`s body. Before its translation into patients, the efficacy of magnetic accumulation must be tested in cell culture systems. To analyze magnetic enrichment under conditions similar to blood flow, we established an experimental in vitro setup with a tumor spheroid placed in a perfused chamber: with this, we showed that it is possible to accumulate cells or chemotherapeutics at the tumor, increasing their therapeutic efficacy. Superparamagnetic iron oxide nanoparticles (SPIONs) are used in nanomedicine as transporter systems for therapeutic cargos, or to magnetize cells to make them magnetically guidable. In cancer treatment, the site-directed delivery of chemotherapeutics or immune effector cells to the tumor can increase the therapeutic efficacy in the target region, and simultaneously reduce toxic side-effects in the rest of the body. To enable the transfer of new methods, such as the nanoparticle-mediated transport from bench to bedside, suitable experimental setups must be developed. In vivo, the SPIONs or SPION-loaded cells must be applied into the blood stream, to finally reach the tumor: consequently, targeting and treatment efficacy should be analyzed under conditions which are as close to in vivo as possible. Here, we established an in vitro method, including tumor spheroids placed in a chamber system under the influence of a magnetic field, and adapted to a peristaltic pump, to mimic the blood flow. This enabled us to analyze the magnetic capture and antitumor effects of magnetically targeted mitoxantrone and immune cells under dynamic conditions. We showed that the magnetic nanoparticle-mediated accumulation increased the anti-tumor effects, and reduced the unspecific distribution of both mitoxantrone and cells. Especially for nanomedical research, investigation of the site-specific targeting of particles, cells or drugs under circulation is important. We conclude that our in vitro setup improves the screening process of nanomedical candidates for cancer treatment.
CRIS-Team WoS Importer:2022-12-30
Keywords: superparamagnetic iron oxide nanoparticles (SPION); magnetic drug targeting (MDT); magnetic cell targeting (MCT)

Journal watch: diagnostic nanoparticles - Poettler, Marina; Cicha, Iwona; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33204

Loading of CAR‐T cells with magnetic nanoparticles for controlled targeting suppresses inflammatory cytokine release and switches tumor cell death mechanism - Pfister, Felix; Carnell, Lucas; Löffler, Lisa; Boosz, Philipp; Schaft, Niels; Dörrie, Jan; Stein, René; Lenz, Malte; Spiecker, Erdmann; Huber, Christian; Haddadin, Sami; Berking, Carola; et al. (MedComm, 2025)
Therapies against hematological malignancies using chimeric antigen receptors (CAR)-T cells have shown great potential; however, therapeutic success in solid tumors has been constrained due to limited tumor trafficking and infiltration, as well as the scarcity of cancer-specific solid tumor antigens. Therefore, the enrichment of tumor-antigen specific CAR-T cells in the desired region is critical for improving therapy efficacy and reducing systemic on-target/off-tumor side effects. Here, we functionalized human CAR-T cells with superparamagnetic iron oxide nanoparticles (SPIONs), making them magnetically controllable for site-directed targeting. SPION-loaded CAR-T cells maintained their specific cytolytic capacity against melanoma cells expressing the CAR-specific antigen chondroitin sulfate proteoglycan (CSPG4). Importantly, SPIONs suppressed cytokine release in the loaded CAR-T cells, shifting the cell death phenotype in the tumor cells from pyroptosis to apoptosis. Furthermore, SPION-loaded CAR-T cells could be enriched in a dynamic flow model through an external magnetic field and be detected in MRI. These results demonstrate that lytic cytotoxicity is retained after SPION-functionalization and provides a basis for future site-specific immunotherapies against solid tumors with reduced systemic adverse side effect

Loading of nuclear autoantigens prototypically recognized by systemic lupus erythematosus sera into late apoptotic vesicles requires intact microtubules and myosin light chain kinase activity - Zirngibl, Matthias; Fuernrohr, B. G.; Janko, Christina; Munoz, L. E.; Voll, R. E.; Gregory, C. D.; Schett, Georg; Herrmann, Martin; Munoz Becerra, Luis (Clinical and Experimental Immunology, 2015)
Most cases of systemic lupus erythematosus (SLE) are characterized by an impaired clearance of apoptotic cells in various tissues. Non-cleared apoptotic waste is considered an immunogen driving the autoimmune response in patients with SLE. During the execution of apoptosis, membrane blebs are formed and filled with cellular components. Here, we evaluate the cytoskeletal pathway(s) responsible for the loading of SLE prototypic nuclear autoantigens into the apoptotic cell-derived membranous vesicles (ACMV) generated during late phases of apoptosis. HeLa cells expressing a fusion protein of histone H2B with green fluorescent protein (GFP) were irradiated with ultraviolet (UV)-B to induce apoptosis. The appearance and trafficking of chromatin-derived material was monitored by fluorescence microscopy. Specific inhibitors of cytoskeletal pathways were employed to identify the motile elements involved in translocation and trafficking of the nuclear components. We observed that immediately after their appearance the ACMV did not contain histone H2B(GFP) ; in this phase the fluorescence was contained in the nuclear remnants and the cytoplasm. Within consecutive minutes the ACMV were loaded with chromatin-derived material, whereas the loading of simultaneously created ACMV with histone H2B(GFP) was not uniform. Some ACMV were preferentially filled and, consequently, showed a remarkably higher histone H2B(GFP) accumulation. Inhibitors of the cytoskeleton revealed that functional microtubules and myosin light chain kinase are required for nuclear shrinkage and loading of nuclear material into the ACMV, respectively.
EVALuna2:12985

Loading of Primary Human T Lymphocytes with Citrate-Coated Superparamagnetic Iron Oxide Nanoparticles Does Not Impair Their Activation after Polyclonal Stimulation - Mühlberger, Marina; Unterweger, Harald; Band, Julia; Lehmann, Christian; Heger, Lukas; Dudziak, Diana; Alexiou, Christoph; Lee, Geoffrey; Janko, Christina (Cells, 2020)
For the conversion of immunologically cold tumors, characterized by a low T cell infiltration, into hot tumors, it is necessary to enrich T cells in the tumor area. One possibility is the use of magnetic fields to direct T cells into the tumor. For this purpose, primary T cells that were freshly isolated from human whole blood were loaded with citrate-coated superparamagnetic iron oxide nanoparticles (SPIONCitrate). Cell toxicity and particle uptake were investigated by flow cytometry and atomic emission spectroscopy. The optimum loading of the T cells without any major effect on their viability was achieved with a particle concentration of 75 mu g Fe/mL and a loading period of 24 h. The cellular content of SPIONCitrate was sufficient to attract these T cells with a magnet which was monitored by live-cell imaging. The functionality of the T cells was only slightly influenced by SPIONCitrate, as demonstrated by in vitro stimulation assays. The proliferation rate as well as the expression of co-stimulatory and inhibitory surface molecules (programmed cell death 1 (PD-1), lymphocyte activation gene 3 (LAG-3), T cell immunoglobulin and mucin domain containing 3 (Tim-3), C-C motif chemokine receptor 7 (CCR7), CD25, CD45RO, CD69) was investigated and found to be unchanged. Our results presented here demonstrate the feasibility of loading primary human T lymphocytes with superparamagnetic iron oxide nanoparticles without influencing their viability and functionality while achieving sufficient magnetizability for magnetically controlled targeting. Thus, the results provide a strong fundament for the transfer to tumor models and ultimately for new immunotherapeutic approaches for cancer treatment.
CRIS-Team WoS Importer:2020-04-21

Lysosome-targeting amplifiers of reactive oxygen species as anticancer prodrugs - Daum, Steffen; Reshetnikov, Viktor; Sisa, Miroslav; Dumych, Tetyana; Lootsik, Maxim D.; Bilyy, Rostyslav; Bila, Evgenia; Janko, Christina; Alexiou, Christoph; Herrmann, Martin; Sellner, Leopold; Mokhir, Andriy (Angewandte Chemie-International Edition, 2017)
Cancer cells produce elevated amounts of reactive oxygen species that has been used to design cancer specific prodrugs. Their activation relies on at least a bimolecular process, where a prodrug reacts with ROS. However, at low µM concentrations of the prodrugs and ROS the activation is usually inefficient. Herein we suggested and validated a potentially general approach for solving this intrinsic problem of ROS-dependent prodrugs. In particular, known 4-(N-ferrocenyl-N-benzylaminocarbonyloxymethyl)phenylboronic acid pinacol ester was converted to its lysosome specific analogue. Since lysosomes contain the higher concentration of active ROS than cytoplasm, activation of the latter prodrug was facilitated with respect to the parent compound. In particular, it was found to exhibit high anticancer activity in a variety of cancer cell lines (IC50 3.5-7.2 µM) and in vivo (40 mg/kg, NK/Ly murine model), but remained weakly toxic towards non-malignant cells (IC50 15-30 µM).
EVALuna2:13450

Magnetic drug targeting reduces the chemotherapeutic burden on circulating leukocytes - Janko, Christina; Dürr, Stephan; Munoz, Luis Enrique; Lyer, Stefan; Chaurio, Ricardo; Tietze, Rainer; Von Loehneysen, Sarah; Schorn, Christine; Herrmann, Martin; Alexiou, Christoph (International Journal of Molecular Sciences, 2013)
Magnetic drug targeting (MDT) improves the integrity of healthy tissues and cells during treatment with cytotoxic drugs. An anticancer drug is bound to superparamagnetic iron oxide nanoparticles (SPION), injected into the vascular supply of the tumor and directed into the tumor by means of an external magnetic field. In this study, we investigated the impact of SPION, mitoxantrone (MTO) and SPIONMTO on cell viability in vitro and the nonspecific uptake of MTO into circulating leukocytes in vivo. MDT was compared with conventional chemotherapy. MTO uptake and the impact on cell viability were assessed by flow cytometry in a Jurkat cell culture. In order to analyze MTO loading of circulating leukocytes in vivo, we treated tumor-bearing rabbits with MDT and conventional chemotherapy. In vitro experiments showed a dose-dependent MTO uptake and reduction in the viability and proliferation of Jurkat cells. MTO and SPIONMTO showed similar cytotoxic activity. Non-loaded SPION did not have any effect on cell viability in the concentrations tested. Compared with systemic administration in vivo, MDT employing SPIONMTO significantly decreased the chemotherapeutic load in circulating leukocytes. We demonstrated that MDT spares the immune system in comparison with conventional chemotherapy. © 2013 by the authors; licensee MDPI, Basel, Switzerland.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Chemotherapy; Immune system; Iron oxide nanoparticles; Leukocytes; Magnetic drug targeting; Mitoxantrone

Magnetic microgels for drug targeting applications: Physical–chemical properties and cytotoxicity evaluation - Turcu, Rodica; Craciunescu, Izabell; Garamus, Vasil M.; Janko, Christina; Lyer, Stefan; Tietze, Rainer; Alexiou, Christoph; Vekas, Ladislau (Journal of Magnetism and Magnetic Materials, 2014)
Magnetoresponsive microgels with high saturation magnetization values have been obtained by a strategy based on the miniemulsion method using high colloidal stability organic carrier ferrofluid as primary material. Hydrophobic nanoparticles Fe3O4/oleic acid are densely packed into well-defined spherical nanoparticle clusters coated with polymers with sizes in the range 40–350 nm. Physical– chemical characteristics of magnetic microgels were investigated by TEM, SAXS, XPS and VSM measurements with the focus on the structure–properties relationship. The impact of magnetic microgels loaded with anticancer drug mitoxantrone (MTO) on the non-adherent human T cell leukemia loaded MTO penetrate into cells and both induce apoptosis and later secondary necrosis in a time- and dose dependent manner. In contrast, microgels without MTO are not cytotoxic in the corresponding concentrations. Our results show that MTO-loaded microgels are promising structures for application in magnetic drug targeting.
EAM Import::2019-03-12

Magnetic nanoparticles for cancer therapy - Dürr, Stephan; Janko, Christina; Lyer, Stefan; Tripal, Philipp; Schwarz, Marc; Zaloga, Jan; Tietze, Rainer; Alexiou, Christoph (Nanotechnology Reviews, 2013)
Cancer is one of the biggest challenges facing the medical research in our time. The goals are to improve not only the therapeutic outcome, even in the cases of advanced and metastatic cancer, but also the methods of treatment, which often have considerable adverse effects. In addition, the current developments, such as demographic change, population growth, and increasing healthcare costs, have to be taken into consideration. In all likelihood, nanotechnology and, in particular, the use of magnetic nanoparticles consisting of the elements nickel, cobalt, and iron can make a significant contribution. The greatest potential can be ascribed to the drug delivery systems: magnetic nanoparticles are functionalized by binding them to various substances, including chemotherapeutic agents, radionuclides, nucleic acids, and antibodies. They can then be guided and accumulated using a magnetic field. Hyperthermia can be induced with an alternating magnetic field, providing another therapeutic option. Magnetic nanoparticles may be useful in overcoming cancer drug resistance. They also contribute to realizing a combination of diagnostic investigation and therapy in the field of " theranostics ". The multifaceted and promising results of research in the recent years offer the prospect of a real advance in cancer therapy in the near future.
Created from Fastlane, Scopus look-up
Keywords: Cancer drug resistance; Cancer therapy; Drug delivery; Hyperthermia; Magnetic nanoparticles

Magnetic nanoparticles for medical applications - Cicha, Iwona; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33163

Magnetic Removal of Candida albicans Using Salivary Peptide-Functionalized SPIONs - Friedrich, Bernhard; Tietze, Rainer; Dümig, Michaela; Sover, Alexandru; Boca, Marius Andrei; Schreiber, Eveline; Band, Julia; Janko, Christina; Krappmann, Sven; Alexiou, Christoph; Lyer, Stefan (International Journal of Nanomedicine, 2023)
Purpose: Magnetic separation of microbes can be an effective tool for pathogen identification and diagnostic applications to reduce the time needed for sample preparation. After peptide functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with an appropriate interface, they can be used for the separation of sepsis-associated yeasts like Candida albicans. Due to their magnetic properties, the magnetic extraction of the particles in the presence of an external magnetic field ensures the accumulation of the targeted yeast. Materials and Methods: In this study, we used SPIONs coated with 3-aminopropyltriethoxysilane (APTES) and functionalized with a peptide originating from GP340 (SPION-APTES-Pep). For the first time, we investigate whether this system is suitable for the separation and enrichment of Candida albicans, we investigated its physicochemical properties and by thermogravimetric analysis we determined the amount of peptide on the SPIONs. Further, the toxicological profile was evaluated by recording cell cycle and DNA degradation. The separation efficiency was investigated using Candida albicans in different experimental settings, and regrowth experiments were carried out to show the use of SPION-APTES-Pep as a sample preparation method for the identification of fungal infections. Conclusion: SPION-APTES-Pep can magnetically remove more than 80% of the microorganism and with a high selective host-pathogen distinction Candida albicans from water-based media and about 55% in blood after 8 minutes processing without compromising effects on the cell cycle of human blood cells. Moreover, the separated fungal cells could be regrown without any restrictions.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Candida albicans; fungal sepsis; GP340; microbiological identification; SPIONs

Magnetic Tissue Engineering for Voice Rehabilitation - First Steps in a Promising Field - Dürr, Stephan; Bohr, Christopher; Poettler, Marina; Lyer, Stefan; Friedrich, Ralf P.; Tietze, Rainer; Döllinger, Michael; Alexiou, Christoph; Janko, Christina (Anticancer Research, 2016)
The voice is one of the most important instruments of communication between humans. It is the product of intact and well-working vocal folds. A defect of these structures causes dysphonia, associated with a clear reduction of quality of life. Tissue engineering of the vocal folds utilizing magnetic cell levitation after nanoparticle loading might be a technique to overcome this challenging problem.Vocal fold fibroblasts (VFFs) were isolated from rabbit larynges and cultured. For magnetization, cells were incubated with superparamagnetic iron oxide nanoparticles (SPION) and the loading efficiency was determined by Prussian blue staining. Biocompatibility was analyzed in flow cytometry by staining with annexin V-fluorescein isothiocyanate propidium iodide, 1,1',3,3,3',3'-hexamethylindodicarbo-cyanine iodide [DiIC1(5)] and propidium idodide-Triton X-100 to monitor phosphatidylserine exposure, plasma membrane integrity, mitochondrial membrane potential and DNA degradation.Isolated VFFs can be successfully loaded with SPION, and optimal iron loading associated with minimized cytotoxicity represents a balancing act in magnetic tissue engineering.Our data are a firm basis for the next steps of investigations. Magnetic tissue engineering using magnetic nanoparticle-loaded cells which form three-dimensional structures in a magnetic field will be a promising approach in the future.
EVALuna2:20008

Magnetic Tissue Engineering of the Vocal Fold Using Superparamagnetic Iron Oxide Nanoparticles - Poettler, Marina; Fliedner, Anna; Bergmann, Julia; Bui, Linh Katrin; Mühlberger, Marina; Braun, Christian; Graw, Matthias; Janko, Christina; Friedrich, Oliver; Alexiou, Christoph; Lyer, Stefan (Tissue Engineering: Parts A, B, and C, 2019)
Losing one's ability to speak, because of tissue deficiency at the vocal fold (VF), leads to serious impairment in the quality of life. Until now, there is no successful approach for regenerating the VF. The aim of this study was to show the advantage of magnetic nanoparticles in the generation of scaffold-free three-dimensional (3D) VF cell constructs by magnetic tissue engineering (MTE). Rabbit VF fibroblasts were used to establish MTE: after cellular uptake of superparamagnetic iron oxide nanoparticles (SPIONs), cells can be controlled with a magnetic field thereby forming solid 3D cell structures. To transfer this method into human cells, SPIONs were adapted accordingly and tested for their influence on human VF (hVF) cells and for their ability to perform MTE with hVF cells. Of interest, the cell number and the magnet's shape influence the form of the rabbit VF cell construct. After successful characterization of hVF cells, biocompatibility analyses revealed no significant influence of SPIONs on them, thus 3D hVF cell constructs could be successfully generated by MTE. These basic results are important to develop MTE as an innovative method to regenerate functional VFs. We expect that in vivo studies, including MTE as an elegant, far-field controlled and touchless technology, will translate MTE VF bioconstructs into reconstructive laryngeal medicine. Impact Statement This study aims at nanotechnology for regenerative medicine by magnetic tissue engineering (MTE). New approaches for vocal fold (VF) reconstruction are desperately needed. Superparamagnetic iron oxide nanoparticles offer innovative, scaffold-free potentials for tissue engineering: MTE. By using MTE we could generate functional multilayered human VF cell constructs, which can consequently be used to regenerate the voice in patients with VF injuries.
CRIS-Team WoS Importer:2019-05-14

Mitoxantrone and Mitoxantrone-Loaded Iron Oxide Nanoparticles Induce Cell Death in Human Pancreatic Ductal Adenocarcinoma Cell Spheroids - Dinter, Jonas; Friedrich, Ralf P.; Yang, Hai; Pilarsky, Christian; Mangge, Harald; Pöttler, Marina; Janko, Christina; Alexiou, Christoph; Lyer, Stefan (Materials, 2023)
Pancreatic ductal adenocarcinoma is a hard-to-treat, deadly malignancy. Traditional treatments, such as surgery, radiation and chemotherapy, unfortunately are still not able to significantly improve long-term survival. Three-dimensional (3D) cell cultures might be a platform to study new drug types in a highly reproducible, resource-saving model within a relevant pathophysiological cellular microenvironment. We used a 3D culture of human pancreatic ductal adenocarcinoma cell lines to investigate a potential new treatment approach using superparamagnetic iron oxide nanoparticles (SPIONs) as a drug delivery system for mitoxantrone (MTO), a chemotherapeutic agent. We established a PaCa DD183 cell line and generated PANC-1SMAD4 (−/−) cells by using the CRISPR-Cas9 system, differing in a prognostically relevant mutation in the TGF-β pathway. Afterwards, we formed spheroids using PaCa DD183, PANC-1 and PANC-1SMAD4 (−/−) cells, and analyzed the uptake and cytotoxic effect of free MTO and MTO-loaded SPIONs by microscopy and flow cytometry. MTO and SPION–MTO-induced cell death in all tumor spheroids in a dose-dependent manner. Interestingly, spheroids with a SMAD4 mutation showed an increased uptake of MTO and SPION–MTO, while at the same time being more resistant to the cytotoxic effects of the chemotherapeutic agents. MTO-loaded SPIONs, with their ability for magnetic drug targeting, could be a future approach for treating pancreatic ductal adenocarcinomas.
CRIS-Team Scopus Importer:2023-04-28
Keywords: 3D cell culture; magnetic drug targeting; nanomedicine; pancreatic ductal adenocarcinoma; superparamagnetic iron oxide nanoparticles

Mitoxantrone-loaded nanoparticles for magnetically controlled tumor therapy–induction of tumor cell death, release of danger signals and activation of immune cells - Ratschker, Teresa; Egenberger, Laura; Alev, Magdalena; Zschiesche, Lisa; Band, Julia; Schreiber, Eveline; Frey, Benjamin; Derer, Anja; Alexiou, Christoph; Janko, Christina (Pharmaceutics, 2020)
Stimulating the patient`s immune system represents a promising therapeutic strategy to fight cancer. However, low immunogenicity of the tumor cells within an immune suppressive milieu often leads to weak anti-tumor immune responses. Additionally, the immune system may be impaired by accompanying aggressive chemotherapies. We show that mitoxantrone, bound to superparamagnetic iron oxide nanoparticles (SPIONs) as the transport system, can be magnetically accumulated in adherent HT-29 colon carcinoma cells, thereby inducing the same cell death phenotype as its soluble counterpart, a chemotherapeutic agent and prototypic inductor of immunogenic cell death. The nanoparticle-loaded drug induces cell cycle stop, apoptosis and secondary necrosis in a dose-and time-dependent manner comparable to the free drug. Cell death was accompanied by the release of interleukin-8 and damage-associated molecular patterns (DAMPs) such as HSP70 and ATP, which fostered chemotactic migration of monocytes and maturation of dendritic cells. We furthermore ensured absence of endotoxin contaminations and compatibility with erythrocytes and platelets and investigated the influence on plasma coagulation in vitro. Summarizing, with magnetic enrichment, mitoxantrone can be accumulated at the desired place, sparing healthy peripheral cells and tissues, such as immune cells. Conserving immune competence in cancer patients in the future might allow combined therapeutic approaches with immune therapies (e.g. checkpoint inhibitors).
CRIS-Team Scopus Importer:2020-10-09
Keywords: Cell death; Chemotherapy; Iron oxide nanoparticles; Magnetic drug targeting; Nanomedicine

Modulation of immune responses by nanoparticles - Janko, Christina; Friedrich, Ralf P.; Cicha, Iwona; Unterweger, Harald; Lyer, Stefan; Alexiou, Christoph (Nanomedicine, 2021)
CRIS-Team WoS Importer:2021-08-27

N-Alkylaminoferrocene-Based Prodrugs Targeting Mitochondria of Cancer Cells - Reshetnikov, Viktor; Özkan, Hülya; Daum, Steffen; Janko, Christina; Alexiou, Christoph; Sauer, Caroline; Heinrich, Markus; Mokhir, Andriy (Molecules, 2020)
Intracellular concentration of reactive oxygen species (e.g., H2O2) in cancer cells is elevated over 10-fold as compared to normal cells. This feature has been used by us and several other research groups to design cancer specific prodrugs, for example, N-alkylaminoferrocene (NAAF)-based prodrugs. Further improvement of the efficacy of these prodrugs can be achieved by their targeting to intracellular organelles containing elevated reactive oxygen species (ROS) amounts. For example, we have previously demonstrated that lysosome-targeted NAAF-prodrugs exhibit higher anticancer activity in cell cultures, in primary cells and in vivo (Angew. Chem. Int. Ed. 2017, 56, 15545). Mitochondrion is an organelle, where electrons can leak from the respiratory chain. These electrons can combine with O2, generating O2-• that is followed by dismutation with the formation of H2O2. Thus, ROS can be generated in excess in mitochondria and targeting of ROS-sensitive prodrugs to these organelles could be a sensible possibility for enhancing their efficacy. We have previously reported on NAAF-prodrugs, which after their activation in cells, are accumulated in mitochondria (Angew. Chem. Int. Ed. 2018, 57, 11943). Now we prepared two hybrid NAAF-prodrugs directly accumulated in mitochondria and activated in these organelles. We studied their anticancer activity and mode of action. Based on these data, we concluded that ROS produced by mitochondria is not available in sufficient quantities for activation of the ROS-responsive prodrugs. The reason for this can be efficient scavenging of ROS by antioxidants. Our data are important for the understanding of the mechanism of action of ROS-activatable prodrugs and will facilitate their further development.
CRIS-Team Scopus Importer:2020-06-16
Keywords: cancer; mitochondrion; N-alkylaminoferrocene; prodrug; reactive oxygen species

Nanocarriers for therapeutic phytochemicals - Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Tietze, Rainer; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2024)
Phytochemicals are natural bioactive compounds produced by plants. Their role is to protect the host from pathogens or predators and, as the components of herbal remedies, they have been used since antiquity in traditional medicine, showing e.g. anti-inflammatory, antibacterial, antiviral, or lipid-lowering properties. Despite the growing interest in this class of drugs, a large gap exists between the expected activity of the phytochemicals and their effective use in therapies, mainly due to their poor bioavailability upon oral administration and individual differences in metabolism. Encapsulating these potent substances in nanocarriers that enable extended circulation time, or provide enteric coating to protect the orally administered phytochemicals, is expected to increase the bioavailability of the drugs and potentially allow their controlled release. This article highlights some recent reports addressing the development of nanocarriers for phytochemicals with therapeutic potential in human disease
CRIS-Team Scopus Importer:2024-09-27
Keywords: acute pancreatitis; cancer therapy; dry eye disease; nanosystems; pancreatic cancer; phytochemical drugs; ulcerative colitis

'Nano-lysing' the disease process: novel diagnostic and therapeutic nanoparticles - Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Lyer, Stefan; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2018)
EVALuna2:35455

Nanomaterial-based ophthalmic therapies - Unterweger, Harald; Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Tietze, Rainer; Friedrich, Bernhard; Alexiou, Christoph (Nanomedicine, 2023)
CRIS-Team Scopus Importer:2023-09-01
Keywords: age-related macular degeneration; diabetic retinopathy; eye infections; glaucoma; keratitis; nanoparticles

Nanomedical innovation: the SEON-concept for an improved cancer therapy with magnetic nanoparticles - Lyer, Stefan; Tietze, Rainer; Unterweger, Harald; Zaloga, Jan; Singh, Raminder; Matuszak, Jasmin; Poettler, Marina; Friedrich, Ralf P.; Dürr, Stephan; Cicha, Iwona; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2015)
Nanomedicine offers tremendous opportunities for the development of novel therapeutic and diagnostic tools. During the last decades, extensive knowledge was gained about stabilizing and the coating of nanoparticles, their functionalization for drug binding and drug release and possible strategies for therapies and diagnostics of different diseases. Most recently, more and more emphasis has been placed on nanotoxicology and nanosafety aspects. The section of experimental oncology and nanomedicine developed a concept for translating this knowledge into clinical application of magnetic drug targeting for the treatment of cancer and other diseases using superparamagnetic iron oxide nanoparticles. This approach includes reproducible synthesis, detailed characterization, nanotoxicological testing, evaluation in ex vivo models, preclinical animal studies and production of superparamagnetic iron oxide nanoparticles according to good manufacturing practice regulations.
EVALuna2:19990

Nanomedicine for cardiovascular disorders - Cicha, Iwona; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Pöttler, Marina; Alexiou, Christoph (Nanomedicine, 2019)
CRIS-Team Scopus Importer:2019-12-31
Keywords: aneurysm; atherothrombosis; cardiovascular diseases; metabolic disease; myocardial infarction; stroke

Nanomedicine for neuroprotection - Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Unterweger, Harald; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2018)
EVALuna2:35446

Nanomedicine for vaccination and diagnosis of diseases - Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2021)
CRIS-Team Scopus Importer:2021-03-05
Keywords: cancer; disease detection; immunotherapy; vaccinations; viral infections

Nanoparticles for regenerative medicine - Pöttler, Marina; Cicha, Iwona; Unterweger, Harald; Janko, Christina; Friedrich, Ralf P.; Alexiou, Christoph (Nanomedicine, 2019)
CRIS-Team Scopus Importer:2019-08-20
Keywords: cilia restoration; nanoparticles for functional recovery; osteogenesis; remyelination; tissue regeneration

Nanoparticles for the treatment of inflammatory conditions - Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Unterweger, Harald; Alexiou, Christoph (Nanomedicine, 2024)
CRIS-Team Scopus Importer:2024-02-16
Keywords: cytokine storm; drug delivery; hypertension; inflammation; ischemia–reperfusion injury; nanosystems; periodontitis; pneumonia

Non-immunogenic dextran-coated superparamagnetic iron oxide nanoparticles: a biocompatible, size-tunable contrast agent for magnetic resonance imaging - Unterweger, Harald; Janko, Christina; Schwarz, Marc; Dezsi, Laszlo; Urbanics, Rudolf; Matuszak, Jasmin; Orfi, Erik; Fülöp, Tamás; Bäuerle, Tobias; Szebeni, Janos; Journe, Clement; Boccaccini, Aldo R.; et al. (International Journal of Nanomedicine, 2017)

Non-magnetic chromatographic separation of colloidally metastable superparamagnetic iron oxide nanoparticles and suspension cells - Mühlberger, Marina; Janko, Christina; Unterweger, Harald; Band, Julia; Schreiber, Eveline; Lehmann, Christian; Dudziak, Diana; Lee, Geoffrey; Alexiou, Christoph; Tietze, Rainer (Journal of Chromatography B-Analytical Technologies in the Biomedical and Life Sciences, 2019)
For magnetic control of cells for biomedical applications such as targeting of immune cells to tumors, cells must be magnetizable. For that, cells are incubated with superparamagnetic iron oxide nanoparticles (SPIONs)to take them up and thus become magnetizable. When using adherent cells, non-ingested SPIONs can be easily removed by rinsing of the particles regardless of their colloidal stability in cell culture medium. However, if suspension cells such as T cells are to be loaded with SPIONs, established methods to separate excess nanoparticles from cells are based on physicochemical parameters such as density, size or magnetizability. Thus, colloidal stability of the particles is of great importance, since only colloidally stable SPIONs can be completely separated from the cells due to their physicochemical differences. Aggregates of colloidally meta- or unstable particles cannot, however, be separated from cells due to their overlapping sizes and densities. Thus, development of an alternative method for the separation of nanoparticle aggregates from suspension cells is urgently needed. Here, we present an affinity chromatographic separation method based on immunohistochemical properties of the respective cells. A desthiobiotinylated antibody against a cellular surface antigen (here CD90.2 receptor on EL4 T cells)is immobilized on a streptavidin agarose column optimized for cell purification. Subsequently the column is loaded with the particle/cell suspension so that the cells bind to the column. After removing the particles by washing, the cells can be gently eluted with biotin solution under physiological conditions. This allows >95% of the excess iron concentration to be removed while maintaining cell viability.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Affinity chromatography; Antibody; Biotin; Cell viability; Desthiobiotin; Streptavidin

Novel nanoparticulate drug delivery systems - Friedrich, Ralf P.; Pöttler, Marina; Cicha, Iwona; Lyer, Stefan; Janko, Christina; Alexiou, Christoph (Nanomedicine, 2016)
EVALuna2:33375

Optical Microscopy Systems for the Detection of Unlabeled Nanoparticles - Friedrich, Ralf P.; Kappes, Mona; Cicha, Iwona; Tietze, Rainer; Braun, Christian; Schneider-Stock, Regine; Nagy, Roland; Alexiou, Christoph; Janko, Christina (International Journal of Nanomedicine, 2022)
Label-free detection of nanoparticles is essential for a thorough evaluation of their cellular effects. In particular, nanoparticles intended for medical applications must be carefully analyzed in terms of their interactions with cells, tissues, and organs. Since the labeling causes a strong change in the physicochemical properties and thus also alters the interactions of the particles with the surrounding tissue, the use of fluorescently labeled particles is inadequate to characterize the effects of unlabeled particles. Further, labeling may affect cellular uptake and biocompatibility of nanoparticles. Thus, label-free techniques have been recently developed and implemented to ensure a reliable characterization of nanoparticles. This review provides an overview of frequently used label-free visualization techniques and highlights recent studies on the development and usage of microscopy systems based on reflectance, darkfield, differential interference contrast, optical coherence, photothermal, holographic, photoacoustic, total internal reflection, surface plasmon resonance, Rayleigh light scattering, hyperspectral and reflectance structured illumination imaging. Using these imaging modalities, there is a strong enhancement in the reliability of experiments concerning cellular uptake and biocompatibility of nanoparticles, which is crucial for preclinical evaluations and future medical application
Keywords: label free imaging; nanoparticle detection; non-fluorescent imaging; reflectance imaging; holotomography; scattering microscopy

Orally administered nanoparticles for gastrointestinal applications - Tietze, Rainer; Unterweger, Harald; Janko, Christina; Civelek, Mehtap; Cicha, Iwona; Spielvogel, Helmut; Alexiou, Christoph (Nanomedicine, 2023)
CRIS-Team WoS Importer:2023-03-24

Peptide functionalized magnetic nanoparticles for experimental sepsis therapy - Friedrich, Bernhard; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Alexiou, Christoph; Tietze, Rainer (INFECTION, 2019)
CRIS-Team WoS Importer:2019-09-06

Real-time cell analysis of human cancer cell lines after chemotherapy with functionalized magnetic nanoparticles - Dürr, Stephan; Lyer, Stefan; Mann, Johannes; Janko, Christina; Tietze, Rainer; Schreiber, Eveline; Herrmann, Martin; Alexiou, Christoph (Anticancer Research, 2012)
Background: Magnetic drug targeting is a new and innovative approach in cancer treatment. In order to avoid the adverse effects of chemotherapy, the therapeutic agent is linked to superparamagnetic nanoparticles which are injected into a tumour-supporting artery and is focused by an external magnetic field to the tumour region in order to provoke maximum local impact. Analysis of nanoparticles and chemotherapeutic substances in human cancer cell culture is necessary to provide respective information for in vivo applications. Materials and Methods: The effect of pure mitoxantrone and mitoxantrone bound to nanoparticles was tested on human cancer cell lines using real-time cell analysis (RTCA) and lactate dehydrogenase (LDH) assays. RTCA was performed by impedance measuring. The impedance is expressed as the cell index (CI), which is a parameter of cell viability. Results: RTCA showed that mitoxantrone when bound to nanoparticles was more toxic than the drug alone. The CI clearly decreased faster after adding the chemotherapeutic bound to nanoparticles than when adding the pure drug alone. However, in the first experiments, the particles themselves showed no toxicity at therapeutically relevant concentrations. These results were confirmed by LDH assays. Conclusion: The toxic effects of chemotherapeutic agents (e.g. mitoxantrone) on human cancer cell lines (e.g. MCF-7) can be enhanced if these drugs are bound to magnetic nanoparticles. These preliminary data show a dependency on the different application modes of RTCA. The results presented here are a first step for a better understanding of the effectiveness of magnetic drug targeting as a new and innovative cancer treatment.
CRIS-Team Scopus Importer:2022-06-27
Keywords: Cell culture; Magnetic drug targeting MCF-7 breast cancer cells; Magnetic nanoparticles; Real-time cell analysis

Recent nanomedicine articles of outstanding interest: nanoparticle functionalization for disease diagnostics and therapy - Janko, Christina; Pöttler, Marina; Friedrich, Ralf P.; Lyer, Stefan; Cicha, Iwona; Alexiou, Christoph (Nanomedicine, 2015)
EVALuna2:19956

Redox modulation of HMGB1-related signaling - Janko, Christina; Filipovic, Milos; Munoz Becerra, Luis; Schorn, Christine; Schett, Georg; Ivanovic-Burmazovic, Ivana; Herrmann, Martin (Antioxidants & Redox Signaling, 2014)
Significance: In the cells' nuclei, high-mobility group box protein 1 (HMGB1) is a nonhistone chromatin-binding protein involved in the regulation of transcription. Extracellularly, HMGB1 acts as a danger molecule with properties of a proinflammatory cytokine. It can be actively secreted from myeloid cells or passively leak from any type of injured, necrotic cell. Increased serum levels of active HMGB1 are often found in pathogenic inflammatory conditions and correlate with worse prognoses in cancer, sepsis, and autoimmunity. By damaging cells, superoxide and peroxynitrite promote leakage of HMGB1. Recent Advances: The activity of HMGB1 strongly depends on its redox state: Inflammatory-active HMGB1 requires an intramolecular disulfide bond (Cys23 and Cys45) and a reduced Cys106. Oxidation of the latter blocks its stimulatory activity and promotes immune tolerance. Critical Issues: Reactive oxygen and nitrogen species create an oxidative environment and can be detoxified by superoxide dismutase (SOD), catalase, and peroxidases. Modifications of the oxidative environment influence HMGB1 activity. Future Directions: In this review, we hypothesize that manipulations of an oxidative environment by SOD mimics or by hydrogen sulfide are prone to decrease tissue damage. Both the concomitant decreased HMGB1 release and its redox chemical modifications ameliorate inflammation and tissue damage. Antioxid. Redox Signal. 20, 1075-1085. © Mary Ann Liebert, Inc.

ROS-Responsive N-Alkylaminoferrocenes for Cancer-Cell-Specific Targeting of Mitochondria - Reshetnikov, Viktor; Daum, Steffen; Janko, Christina; Karawacka, Weronika; Tietze, Rainer; Alexiou, Christoph; Paryzhak, Solomiya; Dumych, Tetiana; Bilyy, Rostyslav; Tripal, Philipp; Schmid, Benjamin; Palmisano, Ralf; et al. (Angewandte Chemie International Edition, 2018)
Mitochondrial membrane potential is more negative in cancer cells than in normal cells, allowing cancer targeting by delocalized lipophilic cations (DLCs). However, as the difference is rather small, these drugs affect also normal cells. Now a concept of pro-DLCs is proposed based on an N-alkylaminoferrocene structure. These prodrugs are activated by the reaction with reactive oxygen species (ROS) forming ferrocenium-based DLCs. Since ROS are overproduced in cancer, the high-efficiency cancer-cell-specific targeting of mitochondria could be achieved as demonstrated by fluorescence microscopy in combination with two fluorogenic pro-DLCs in vitro and in vivo. We prepared a conjugate of another pro-DLC with a clinically approved drug carboplatin and confirmed that its accumulation in mitochondria was higher than that of the free drug. This was reflected in the substantially higher anticancer effect of the conjugate.
EVALuna2:35451

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

Selection of potential iron oxide nanoparticles for breast cancer treatment based on in vitro cytotoxicity and cellular uptake - Poller, Johanna; Zaloga, Jan; Schreiber, Eveline; Unterweger, Harald; Janko, Christina; Radon, Patricia; Eberbeck, Dietmar; Trahms, Lutz; Alexiou, Christoph; Friedrich, Ralf P. (International Journal of Nanomedicine, 2017)
Superparamagnetic iron oxide nanoparticles (SPIONs) are promising tools for the treatment of different diseases. Their magnetic properties enable therapies involving magnetic drug targeting (MDT), hyperthermia or imaging. Depending on the intended treatment, specific characteristics of SPIONs are required. While particles used for imaging should circulate for extended periods of time in the vascular system, SPIONs intended for MDT or hyperthermia should be accumulated in the target area to come into close proximity of, or to be incorporated into, specific tumor cells. In this study, we determined the impact of several accurately characterized SPION types varying in size, zeta potential and surface coating on various human breast cancer cell lines and endothelial cells to identify the most suitable particle for future breast cancer therapy. We analyzed cellular SPION uptake, magnetic properties, cell proliferation and toxicity using atomic emission spectroscopy, magnetic susceptometry, flow cytometry and microscopy. The results demonstrated that treatment with dextran-coated SPIONs (SPIONDex) and lauric acid-coated SPIONs (SPIONLA) with an additional protein corona formed by human serum albumin (SPIONLA-HSA) resulted in very moderate particle uptake and low cytotoxicity, whereas SPIONLAhad in part much stronger effects on cellular uptake and cellular toxicity. In summary, our data show significant dose-dependent and particle type-related response differences between various breast cancer and endothelial cells, indicating the utility of these particle types for distinct medical applications.
EVALuna2:33205

Sialylation of anti-histone immunoglobulin G autoantibodies determines their capabilities to participate in the clearance of late apoptotic cells - Magorivska, I.; Munoz Becerra, Luis; Janko, Christina; Dumych, Tetiana; Rech, J.; Schett, Georg; Nimmerjahn, Falk; Bilyy, R.; Herrmann, Martin (Clinical and Experimental Immunology, 2016)
The Fc portion of immunoglobulin (Ig)G harbours a single glycosylation site. Glycan sialylation is critical for structure and for certain effector functions of IgG. Anti-histone IgG of patients with systemic lupus erythematosus is reportedly responsible for the recruitment of polymorphonuclear cells (PMN) to the clearance of apoptotic cells. Autoantibodies decorating secondary necrotic cells (SNEC) induce proinflammatory responses after activation of blood-borne phagocytes. Analysing the sialylation status of affinity-purified anti-histone IgG in patients with systemic lupus erythematosus (SLE), we demonstrated that the anti-histone IgG was contained preferentially in the non-sialylated fraction. In functional ex-vivo phagocytosis studies, non-sialylated anti-SNEC IgG directed SNEC preferentially into PMN but did not change their cytokine secretion profiles. In contrast, sialylated IgG reduced the phagocytosis by monocytes of SNEC. Moreover, the sialylated anti-SNEC IgG was not simply anti-inflammatory, but switched the cytokine secretion profiles from interleukin (IL)-6/IL-8 to tumour necrosis factor (TNF)-/IL-1. Here we describe how different sialylation statuses of IgG autoantibodies contribute to the complex inflammatory network that regulates chronic inflammation.
Keywords: autoantibodies; IgG; lectin; sialylation; SLE

Sol-gel derived B2O3-CaO borate bioactive glasses with hemostatic, antibacterial and pro-angiogenic activities - Zheng, Kai; Bider, Faina; Monavari, Mahshid; Xu, Zhiyan; Janko, Christina; Alexiou, Christoph; Beltrán, Ana M.; Boccaccini, Aldo R. (Regenerative Biomaterials, 2024)
Sol-gel borate bioactive glasses (BGs) are promising ion-releasing biomaterials for wound healing applications. Here, we report the synthesis of a series of binary B2O3-CaO borate BGs (CaO ranging from 50 to 90 mol%) using a sol-gel-based method. The influence of CaO content in B2O3-CaO borate BG on morphology, structure and ion release behavior was investigated in detail. Reduced dissolution (ion release) and crystallization could be observed in borate BGs when CaO content increased, while the morphology was not significantly altered by increasing CaO content. Our results evidenced that the ion release behavior of borate BGs could be tailored by tuning the B2O3/CaO molar ratio. We also evaluated the in vitro cytotoxicity, hemostatic, antibacterial and angiogenic activities of borate BGs. Cytocompatibility was validated for all borate BGs. However, borate BGs exhibited composition-dependent hemostatic, antibacterial and angiogenic activities. Generally, higher contents of Ca in borate BGs facilitated hemostatic activity, while higher contents of B2O3 were beneficial for pro-angiogenic activity. The synthesized sol-gel-derived borate BGs are promising materials for developing advanced wound healing dressings, given their fast ion release behavior and favorable hemostatic, antibacterial and angiogenic activities.
CRIS-Team Scopus Importer:2024-02-02
Keywords: borate glasses; glass composition; sol-gel processing; wound healing

SPIONs and magnetic hybrid materials: Synthesis, toxicology and biomedical applications - Friedrich, Ralf P.; Janko, Christina; Unterweger, Harald; Lyer, Stefan; Alexiou, Christoph (Physical Sciences Review, 2021)
In the past decades, a wide variety of different superparamagnetic iron oxide nanoparticles (SPIONs) have been synthesized. Due to their unique properties, such as big surface-to-volume ratio, superparamagnetism and comparatively low toxicity, they are principally well suited for many different technical and biomedical applications. Meanwhile, there are a numerous synthesis methods for SPIONs, but high requirements for biocompatibility have so far delayed a successful translation into the clinic. Moreover, depending on the planned application, such as for imaging, magnetic drug targeting, hyperthermia or for hybrid materials intended for regenerative medicine, specific physicochemical and biological properties are inevitable. Since a summary of all existing SPION systems, their properties and application is far too extensive, this review reports on selected methods for SPION synthesis, their biocompatibility and biomedical applications.
CRIS-Team WoS Importer:2022-01-14

SPIONs functionalized with small peptides for binding of lipopolysaccharide, a pathophysiologically relevant microbial product. - Karawacka, Weronika; Janko, Christina; Unterweger, Harald; Mühlberger, Marina; Lyer, Stefan; Taccardi, Nicola; Mokhir, Andriy; Jira, Wolfgang; Peukert, Wolfgang; Boccaccini, Aldo R.; Kolot, Mikhail; Strauss, Richard; et al. (Colloids and Surfaces B-Biointerfaces, 2018)
Systemic inflammation such as sepsis represents an acute life-threatening condition, to which often no timely remedy can be found. A promising strategy may be to functionalize magnetic nanoparticles with specific peptides, derived from the binding motives of agglutinating salivary proteins, that allow immobilization of pathogens. In this work, superparamagnetic iron oxide nanoparticles with stable polycondensed aminoalkylsilane layer were developed, to which the heterobifunctional linkers N-succinimidyl 3-(2-pyridyldithio)-propanoate (SDPD) and N-succinimidyl bromoacetate (SBA) were bound. These linkers were further chemoselectively reacted with the thiol group of singularly present cysteines of selected peptides. The resulting functional nanoparticles underwent a detailed physicochemical characterization. The biocompatibility of the primarily coated aminoalkylsilane particles was also investigated. To test the pathogen-binding efficacy of the particles, the lipopolysaccharide-immobilization capacity of the peptide-coated particles was compared with free peptides. Here, one particle-bound peptide species succeeded in capturing 90% of the toxin, whereas the degree of immobilization of the toxin with a system that varied in the sequence of the peptide dropped to 35%. With these promising results, we hope to develop extracorporeal magnetic clearance systems for removing pathogens from the human body in order to accelerate diagnosis and alleviate acute disease conditions such as sepsis.

Stimuli-responsive nanosystems for enhanced drug delivery and diagnosis - Cicha, Iwona; Tietze, Rainer; Unterweger, Harald; Lyer, Stefan; Janko, Christina; Civelek, Mehtap; Alexiou, Christoph (Nanomedicine, 2022)
CRIS-Team WoS Importer:2022-11-25

Strategies to optimize the biocompatibility of iron oxide nanoparticles - "SPIONs safe by design" - Janko, Christina; Zaloga, Jan; Poettler, Marina; Dürr, Stephan; Eberbeck, Dietmar; Tietze, Rainer; Lyer, Stefan; Alexiou, Christoph (Journal of Magnetism and Magnetic Materials, 2017)
Various nanoparticle systems have been developed for medical applications in recent years. For constant improvement of efficacy and safety of nanoparticles, a close interdisciplinary interplay between synthesis, physicochemical characterizations and toxicological investigations is urgently needed. Based on combined toxicological data, we follow a safe-by design strategy for our superparamagnetic iron oxide nanoparticles (SPION). Using complementary interference-free toxicological assay systems, we initially identified agglomeration tendencies in physiological fluids, strong uptake by cells and improvable biocompatibility of lauric acid (LA)-coated SPIONs (SPIONLA). Thus, we decided to further stabilize those particles by an artificial protein corona consisting of serum albumin. This approach finally lead to increased colloidal stability, augmented drug loading capacity and improved biocompatibility in previous in vitro assays. Here, we show in whole blood ex vivo and on isolated red blood cells (RBC) that a protein corona protects RBCs from hemolysis by SPIONs. (C) 2016 Elsevier B.V. All rights reserved.
EVALuna2:33179

Superparamagnetic iron oxide nanoparticles carrying chemotherapeutics improve drug efficacy in monolayer and spheroid cell culture by enabling active accumulation - Nguyen, Khanh; Nuß, Bianca; Mühlberger, Marina; Unterweger, Harald; Friedrich, Ralf P.; Alexiou, Christoph; Janko, Christina (Nanomaterials, 2020)
Cytotoxic and cytostatic chemotherapeutics act by attacking rapidly dividing tumor cells, predominantly affecting malignant tissue and to a certain degree preserving healthy cells. Nonetheless, severe side effects are caused as quickly proliferating healthy cells such as hematopoietic precursors and mucous membranes are impaired as well. This limits the administered dose and eventually allows tumor cells to escape treatment. In order to increase intratumoral drug concentration and simultaneously reduce systemic side effects, nanoparticles have come into focus as drug carriers. The functionalization of superparamagnetic iron oxide nanoparticles (SPIONs) with chemotherapeutics such as mitoxantrone (MTO) enables targeted drug transport by using magnetic forces. Here, we investigate SPIONs consisting of individual iron oxide cores of 10 nm in diameter and a total hydrodynamic diameter of 53 ± 0.8 nm as a transporting system for MTO. Comparing the killing efficacy in monolayer cell culture and multicellular tumor spheroids of HT-29 cells, we show that spheroids tolerate considerably higher doses of nanoparticle-loaded MTO. Therefore, dose predictions from conventional monolayer cell cultures are often misleading for in vivo applications. This was true for both soluble and nanoparticle-bound MTO. Using flow chambers mimicking in vivo blood flow, we furthermore demonstrate that SPIONs can magnetically accumulate MTO. We conclude that SPIONs can function as an effective delivery platform to increase local drug concentrations, thereby potentially overcoming chemotherapy resistance of cells.
CRIS-Team Scopus Importer:2020-09-11
Keywords: Chemotherapy; Drug resistance; Magnetic drug targeting; Mitoxantrone; Nanomedicine; Superparamagnetic iron oxide nanoparticles; Tumor spheroids

Superparamagnetic Iron Oxide Nanoparticles for Targeted Cell Seeding: Magnetic Patterning and Magnetic 3D Cell Culture - Kappes, Mona; Friedrich, Bernhard; Pfister, Felix; Huber, Christian; Friedrich, Ralf Phillipp; Stein, René; Braun, Christian; Band, Julia; Schreiber, Eveline; Alexiou, Christoph; Janko, Christina (Advanced Functional Materials, 2022)
In regenerative medicine, noncontact manipulation of cells enables new possibilities for tissue engineering. Due to their physicochemical properties, superparamagnetic iron oxide nanoparticles (SPIONs) are used in biomedicine for various applications, e.g., as drug transporters, contrast agents or to make cells maneuverable by magnetic forces. SPIONs attached to and/or taken up by cells enable their magnetic targeting for adoptive immune therapies or tissue engineering. Remote control of different “magnetized” cell types can be used to construct multilayered tissues without the need for a scaffold structure. Here, the suitability of SPIONs with various coatings, such as polyacrylic acid-co-maleic acid (PAM), lauric acid (LA), lauric acid-human serum albumin (HSA), and citrate to magnetize cells is compared with the commercially available NanoShuttle-PL, designed for use in magnetic 3D cell cultures. Depending on the amount of cellular labeling, magnetic control is more or less effective. In particular, PAM- and citrate-coated SPIONs achieve good cellular loading and provide magnetic controllability of cells. In 2D cell culture, the magnetic cargo allows the patterned culture of cells. In 3D, SPIONs enable and accelerate spheroid formation as well as micropatterning using unloaded and loaded cells in parallel.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 3D cell culture; iron oxide nanoparticles; magnetic targeting

Synthesis of Magnetic-Nanoparticle/Ansamitocin Conjugates-Inductive Heating Leads to Decreased Cell Proliferation In Vitro and Attenuation Of Tumour Growth In Vivo - Seidel, Katja; Balakrishnan, Asha; Alexiou, Christoph; Janko, Christina; Komoll, Ronja-Melinda; Wang, Liang-Liang; Kirschning, Andreas; Ott, Michael (Chemistry - A European Journal, 2017)
Conjugates based on nanostructured, superparamagnetic particles, a thermolabile linker and a cytotoxic maytansinoid were developed to serve as a model for tumour-selective drug delivery and release. It combines chemo- with thermal therapy. The linker-modified toxin was prepared by a combination of biotechnology and semisynthesis. Drug release was achieved by hyperthermia through an external oscillating electromagnetic field that induces heat inside the particles. Efficacy of this release concept was demonstrated both for cancer cell proliferation in vitro, and for tumour growth in vivo, in a xenograft mouse model. Biocompatibility studies for these magnetic-nanoparticle/ansamitocin conjugates complement this work.
EVALuna2:33212

Targeting of drug-loaded nanoparticles to tumor sites increases cell death and release of danger signals - Alev, Magdalena; Egenberger, Laura; Mühleisen, Laura; Weigel, Bianca; Frey, Benjamin; Friedrich, Ralf P.; Poettler, Marina; Alexiou, Christoph; Janko, Christina (Journal of Controlled Release, 2018)
Innovative strategies fighting cancer by inducing anti-tumor responses from the immune system are urgently needed. Amongst others, chemotherapeutics from the class of the anthracyclines have been shown to induce death of cancer cells with immunogenic features and triggering immunogenic anti-tumor responses. However, the patient's immune system often becomes severely impaired by the unspecific action of these cytotoxic drugs in systemic chemotherapy, preventing any effective immune reactions. To reduce systemic side effects and to accumulate the drug exclusively in the tumor region, we developed an iron oxide nanoparticle-based system for the magnetically targeted delivery of mitoxantrone to the tumor, which has previously proven its long-term therapeutic efficacy in tumor bearing rabbits. Here, we show in vitro that superparamagnetic iron oxide nanoparticles (SPIONs), loaded with the chemotherapeutic drug mitoxantrone, are able to induce cell death with immunogenic features and concomitant maturation of dendritic cells, comparable to the free drug, whereas unloaded nanoparticles are very biocompatible. We conclude that the targeted delivery of mitoxantrone to the tumor region might be a promising possibility to selectively modulate the tumor microenvironment and to locally stimulate immune responses against the tumor. Thus, SPIONs can be used as a platform to specifically bring immunogenic cell death inducers (e.g. mitoxantrone, hypericin, doxorubicin) to the tumor region by sparing the immune system from their toxic effects.
EVALuna2:35474

The effect of mesoporous bioactive glass nanoparticles incorporating various metallic ions (Cu, Zn, Mn, Te) on wound healing - Pourshahrestani, Sara; Zeimaran, Ehsan; Janko, Christina; Alexiou, Christoph; Kerpes, Andrea; Würz, Adrian; Fischer, Marcus; Kaňková, Hana; Hartmann, Martin; Boccaccini, Aldo R. (Materials Advances, 2024)
Recently, mesoporous bioactive glasses (MBGs) as microparticles or nanoparticles (MBGNs) aroused a great interest owing to their high textural properties and capability to be incorporated with biologically active ions desirable for different stages of wound healing. Considering therapeutic effects of two well-recognized elements (copper and zinc) as well as two less-common elements (manganese and tellurium), in this study, different concentrations of these elements were incorporated into SiO2-CaO MBGNs and their potential for wound healing applications was assessed in vitro. While at a concentration of 5 mg ml−1, the extracts of some MBGNs reduced E. coli and S. aureus bacteria viabilities, normal human dermal fibroblast (NHDF) cell viabilities were negatively affected with extracts of Cu-MBGNs and Te-MBGNs. The nanoparticles also affected hemolysis in a donor-dependent manner and the incorporation of Te into the MBGNs networks increased the hemolysis ratio to more than 5%. Moreover, some of the nanoparticles at concentration of 1 mg ml−1 shortened activated partial thromboplastin time (aPTT) insignificantly compared to pure platelet poor plasma. At higher concentrations of therapeutic elements, the extracts of nanoparticles resulted in the significant slower migration of NHDF cells in the scratch area. The effects of the nanoparticles and their extracts on blood coagulation and NHDF cell migration are thus dependent on the composition and/or applied concentration of nanoparticles. The present results provide information for the design of MBGN compositions of interest for wound healing and highlight the importance of optimization of the nanoparticles dosage and therapeutic ion concentration for acceleration of the wound healing process.
CRIS-Team Scopus Importer:2024-08-09

The involvement of E6, p53, p16, MDM2 and Gal-3 in the clinical outcome of patients with cervical cancer - Stiasny, Annika; Freier, Christoph P.; Kuhn, Christina; Schulze, Sandra; Mayr, Doris; Alexiou, Christoph; Janko, Christina; Wiest, Irmi; Dannecker, Christian; Jeschke, Udo; Kost, Bernd P. (Oncology Letters, 2017)
High-risk human papilloma virus (HPV) is the leading cause of cervical cancer. HPV oncogenes are responsible for the development of malignancy, and the E6 oncoprotein that HPV expresses induces the degradation of tumour suppressor protein p53 (p53). This degradation leads to the upregulation of p16; however, unidentified proteins may also serve a role in the development and progression of cervical cancer. Therefore, the aim of the present study was to analyse the expression levels of E6, p53, p16, MDM2 proto-oncogene (MDM2) and galectin-3 (gal-3) in cervical cancer specimens. A total of 250 cervical cancer tissue slides were used. The expression of E6, p53, p16, MDM2 and gal-3 was analysed with immunohistochemical methods and a semi-quantitative scoring. SPSS software was used for the statistical evaluation of staining results and survival analysis of patients with cervical cancer. Cervical cancer specimens demonstrated significantly increased E6 staining with advanced T-status and increased International Federation of Gynecology and Obstetrics classification. E6, p53 and p16 demonstrated significantly different expression levels in squamous epithelial tissue compared with adenocarcinomas. MDM2 and gal-3 demonstrated positively correlated expression levels in cervical cancer. In addition, gal-3 expression was correlated with poor prognosis in p16-negative cases. A negative correlation between the expression of E6 and a mutated form of p53 was also identified in cervical cancer. p53 mutation was demonstrated to be common in cervical cancer, and gal-3 and MDM2 appeared to act in a combined manner in this type of tumour. As gal-3 is overexpressed in the cervical cancer tissue of patients with poor prognosis, the use of gal-3 inhibitors should be investigated in future studies.
EVALuna2:33377

The Pathogenicity of Anti-β2GP1-IgG Autoantibodies Depends on Fc Glycosylation. - Fickentscher, Christoph; Magorivska, Iryna; Janko, Christina; Biermann, Mona; Bilyy, Rostyslav; Nalli, Cecilia; Tincani, Angela; Medeghini, Veronica; Meini, Antonella; Nimmerjahn, Falk; Schett, Georg; Munoz, Luis E.; et al. (Journal of immunology research, 2015)
To analyze the glycosylation of anti-β2GP1, we investigated purified IgG from healthy children, patients with APS, and asymptomatic adult carriers of antiphospholipid antibodies. We observed that in the sera of healthy children and of patients with APS, IgG3 and IgG2 were predominant, respectively. The potentially protective anti-β2GP1-IgM was lower in the sera of healthy children. Although anti-β2GP1-associated C1q did not differ between children and patients with antiphospholipid syndrome, the associated C3c was significantly higher in the sera of healthy children. This indicates a more efficient clearance of anti-β2GP1 immune complexes in the healthy children. This clearance is not accompanied by inflammation or coagulatory events. It is likely that the most important pathogenic factor of the anti-β2GP1-IgG is related to the different glycosylation observed in healthy and diseased individuals. We detected a significantly higher sialylation of anti-β2GP1-IgG isolated from the sera of healthy children and asymptomatic adults when compared with that of patients with clinically apparent antiphospholipid syndrome. Low sialylated IgG reportedly ameliorates inflammation and inflammation promotes hyposialylation. Thus, both reactions create a vicious circle that precipitates the pathology of the antiphospholipid syndrome including thrombus-formation. We conclude that the increased sialylation of anti-β2GP1-IgG of sera of healthy individuals limits their pathogenicity.

The Progression of Cell Death Affects the Rejection of Allogeneic Tumors in Immune-Competent Mice - Implications for Cancer Therapy - Chaurio Gonzalez, Ricardo Alfredo; Munoz, Luis E.; Maueröder, Christian; Janko, Christina; Harrer, Thomas; Fuernrohr, Barbara G.; Niederweis, Michael; Bilyy, Rostyslav; Schett, Georg; Herrmann, Martin; Berens, Christian (Frontiers in Immunology, 2014)
Large amounts of dead and dying cells are produced during cancer therapy and allograft rejection. Depending on the death pathway and stimuli involved, dying cells exhibit diverse features, resulting in defined physiological consequences for the host. It is not fully understood how dying and dead cells modulate the immune response of the host. To address this problem, different death stimuli were studied in B16F10 melanoma cells by regulated inducible transgene expression of the pro-apoptotic active forms of caspase-3 (revCasp-3), Bid (tBid), and the Mycobacterium tuberculosis-necrosis inducing toxin (CpnTCTD). The immune outcome elicited for each death stimulus was assessed by evaluating the allograft rejection of melanoma tumors implanted subcutaneously in BALB/c mice immunized with dying cells. Expression of all proteins efficiently killed cells in vitro (>90%) and displayed distinctive morphological and physiological features as assessed by multiparametric flow cytometry analysis. BALB/c mice immunized with allogeneic dying melanoma cells expressing revCasp-3 or CpnTCTD showed strong rejection of the allogeneic challenge. In contrast, mice immunized with cells dying either after expression of tBid or irradiation with UVB did not, suggesting an immunologically silent cell death. Surprisingly, immunogenic cell death induced by expression of revCasp-3 or CpnTCTD correlated with elevated intracellular reactive oxygen species (ROS) levels at the time point of immunization. Conversely, early mitochondrial dysfunction induced by tBid expression or UVB irradiation accounted for the absence of intracellular ROS accumulation at the time point of immunization. Although ROS inhibition in vitro was not sufficient to abrogate the immunogenicity in our allo-immunization model, we suggest that the point of ROS generation and its intracellular accumulation may be an important factor for its role as damage associated molecular pattern in the development of allogeneic responses.
EVALuna2:13056

Toxicity of Mitoxantrone-loaded Superparamagnetic Iron Oxide Nanoparticles in a HT-29 Tumour Spheroid Model - Hornung, Annkathrin; Poettler, Marina; Friedrich, Ralf P.; Weigel, Bianca; Dürr, Stephan; Zaloga, Jan; Cicha, Iwona; Alexiou, Christoph; Janko, Christina (Anticancer Research, 2016)
Cancer research is commonly carried out in two-dimensional (2D) cell cultures, which poorly reflect in vivo settings where the growing tumours are exposed to mechanical forces and biochemical gradients. In this study we established a HF-29 colon carcinoma tumor spheroid model to investigate the effect of free mitoxantrone (MTO) and its nanoparticle-bound form (SPION(MTO)) under 3D cell culture conditions.Tumour spheroids were generated by seeding HT-29 colon carcinoma cells on agarose-coated cell culture wells. Growth of the spheroids was monitored daily by transmission microscopy upon treatment with free MTO, SPION(MTO) or unloaded SPION.Unloaded SPION did not affect the spheroid size compared to untreated controls, while both free MTO and SPION(MTO) inhibited growth of the spheroids in a dose- and time-dependent manner. In comparison to free MTO, the effect of SPION(MTO) on spheroid growth was slightly delayed. Further analyses are necessary to investigate if MTO infiltrates spheroids in its nanoparticle-bound form or whether it is released from SPION before infiltration.
EVALuna2:20010

Treatment Efficiency of Free and Nanoparticle-Loaded Mitoxantrone for Magnetic Drug Targeting in Multicellular Tumor Spheroids - Hornung, Annkathrin; Poettler, Marina; Friedrich, Ralf P.; Zaloga, Jan; Unterweger, Harald; Lyer, Stefan; Nowak, Johannes; Odenbach, Stefan; Alexiou, Christoph; Janko, Christina (Molecules, 2015)
Major problems of cancer treatment using systemic chemotherapy are severe side effects. Magnetic drug targeting (MDT) employing superparamagnetic iron oxide nanoparticles (SPION) loaded with chemotherapeutic agents may overcome this dilemma by increasing drug accumulation in the tumor and reducing toxic side effects in the healthy tissue. For translation of nanomedicine from bench to bedside, nanoparticle-mediated effects have to be studied carefully. In this study, we compare the effect of SPION, unloaded or loaded with the cytotoxic drug mitoxantrone (MTO) with the effect of free MTO, on the viability and proliferation of HT-29 cells within three-dimensional multicellular tumor spheroids. Fluorescence microscopy and flow cytometry showed that both free MTO, as well as SPION-loaded MTO (SPION(MTO)) are able to penetrate into tumor spheroids and thereby kill tumor cells, whereas unloaded SPION did not affect cellular viability. Since SPION(MTO) has herewith proven its effectivity also in complex multicellular tumor structures with its surrounding microenvironment, we conclude that it is a promising candidate for further use in magnetic drug targeting in vivo.
EVALuna2:19979

Treat or track: nanoagents in the service of health - Lyer, Stefan; Janko, Christina; Friedrich, Ralf P.; Poettler, Marina; Cicha, Iwona; Alexiou, Christoph (Nanomedicine, 2017)
EVALuna2:33195

Tuning the structure of aminoferrocene-based anticancer prodrugs to prevent their aggregation in aqueous solution - Daum, Steffen; Babiy, Svetlana; Konovalova, Helen; Hofer, Walter; Shtemenko, Alexander; Shtemenko, Natalia; Janko, Christina; Alexiou, Christoph; Mokhir, Andriy (Journal of Inorganic Biochemistry, 2018)
Aminoferrocene-based prodrugs are activated in cancer cells by reactive oxygen species (ROS). They were shown to exhibit high cytotoxicity towards a variety of cancer cell lines and primary cancer cells, but remain not toxic towards non-malignant cells. However, these prodrugs have rather high lipophilicity leading to relatively low water solubility. In particular, an n-octanol/water partition coefficient for the best aminoferrocene-based pro drug (2) was found to be 4.51 +/- 0.03. Though the approaches for decreasing lipophilicity are straightforward and include the addition of polar residues to the drug structure, these modifications also lead to dramatic decrease of cell permeability and, correspondingly, lower the activity of the drug. Therefore, a delicate balance of polar and unpolar groups should be found to reduce lipophilicity without compromising the useful drug properties. In this study we optimized an N-alkyl substituent, which is a key element responsible for the stabilization of the aminoferrocene drug released in cancer cells from prodrug 2. We found that an N-propargyl residue is an optimal replacement for the N-benzyl fragment. In particular, such a substitution (prodrug 7a) leads to reduction of prodrug lipophilicity down to logP = 3.78 +/- 0.05, improvement of its water solubility, decrease of its propensity towards aggregation and dramatic increase of its ROS-generating properties. Finally, we demonstrated that the optimized prodrug strongly suppresses growth of Guerin's carcinoma (T8) in vivo at the dose of 30 mg/kg.
EVALuna2:213359